Combined membrane aeration and membrane filtration for space-efficient nitrogen control in reuse-oriented biological pretreatment - Hsin-Chieh Lin; Ting-Wei Wu; Yu-Tzu Huang; Ho Kyong Shon; Chia-Hung Hou (Desalination, 2026)

Nutrient recovery from source-separated urine through ammonia stripping prior to membrane bioreactor - Weonjung Sohn; A.H. Shafaghat; Hsin-Chieh Lin; Sherub Phuntsho; Jing Guan; Xiaodong Jia; Ying Zhang; Ho Kyong Shon (Desalination, 2026)

The role of Mir-365-5p in regulating NF2-Mediated apoptosis and ROS production in hypoxic cardiomyoblasts - Chih-Hsueh Lin; Wei-Yun Wang; Bruce Chi-Kang Tsai; Wei-Wen Kuo; Chia-Hua Kuo; Kuan-Ho Lin; Tsung-Jung Ho; Pei-Ying Pai; Dennis Jine-Yuan Hsieh; Chih-Yang Huang; Shinn-Zong Lin (Molecular Biology Reports, 2026)

Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Prediction of anaerobic chicken manure digestion performance using machine learning algorithms - Chih-Chao Ho; Wen Yi Lin; Cing-Hong Yang; Chiu-Yue Lin; Peer Mohamed Abdul; Setyo Budi Kurniawan; Chyi-How Lay (Biomass and Bioenergy, 2026)

Pilot-scale demonstration and feasibility study of nutrient recovery from human urine in a membrane bioreactor under acidic pH and elevated MLSS conditions - Andrea Merenda; A.H. Shafaghat; Weonjung Sohn; Hsin-Chieh Lin; Mohammad Mahbub Kabir; M. Mozammel Hoque; Sherub Phuntsho; Ho Kyong Shon (Journal of Water Process Engineering, 2026)

Enhanced simulations of overland-gully-sewer flow interactions in coupled three-layer dual drainage modeling - Chia-Ho Wang; Hsiang-Lin Yu; Tsang-Jung Chang; Albert S. Chen (Journal of Hydrology, 2026)

DataNet: linking multi-faceted building energy datasets for effective performance analysis at scale - Hye-Gi Kim; Hyery Shin; Han-Gyeong Chu; Dong Hyuk Yi; Sang-Lin Park; Doosung Kim; Hyunwoo Lim; Sungmin Yoon; Eui-Jong Kim; Jaewan Joe; Sunsook Kim; Hyeunguk Ahn; et al. (Energy and Buildings, 2026)

Integrative study of acute ammonia exposure on the skin of the Striped catfish (Pangasianodon hypophthalmus) - Wei-Hsuan Hsiao; Shun-Yi Lin; Ying-Hsien Wu; Han-Chen Ho; Tsunglin Liu; Liang-Chun Wang (Aquatic Toxicology, 2026)

Multiscale drivers of arthropod functional guilds in rice agroecosystems: Evaluating the roles of climatic, landscape, and management factors - Yu-Pin Lin; Pei-Chen Lin; Shafira Wuryandani; Chun-Chia Liu; Chiao-Ming Lin; Chi-Wei Tsai; Chi-Lun Huang; Chuan-Kai Ho; Gerard H. Ros (Agriculture, Ecosystems & Environment, 2026)

Glucose-derived carbon-confined cu nanoparticles for selective nitrate reduction to ammonia under acidic conditions and biofouling-resistant wastewater treatment - Tsung-Ying Yang; Ko-Shan Ho; Kan-Yen Hsieh; Yu-Lin Hsiao; Sheng-Ci Jhong; Hsiu-Chung Tu (Journal of Water Process Engineering, 2026)

Non-contact discharge estimation using physics-informed neural networks and CNN-enhanced image velocimetry - Yen-Cheng Lin; Cheng-Wei Wu; Hao-Che Ho (Journal of Hydrology, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Targeting the NOX4/NLRP inflammasome axis confers protection by isoliquiritigenin against H2O2-induced synovial inflammation - Yu-Chun Chang; Wei-Wen Kuo; Yen-Pin Chen; Shih-Wen Kao; Dennis Jine-Yuan Hsieh; Tsung-Jung Ho; Chia-Hua Kuo; Chien-Yao Fu; Chih-Yang Huang; Shinn-Zong Lin (Chemico-Biological Interactions, 2026)

Leaf surface structure shapes herbivore preference and predation efficiency: leaf-mediated biocontrol in a soybean system - Wei-Jiun Lin; Jo-Shih Chiu; Chuan-Kai Ho (Journal of Pest Science, 2026)

Nitrification performance and microbial community analysis in membrane-aerated biofilm reactors for valorization of liquid anaerobic digestate - A.H. Shafaghat; Hsin-Chieh Lin; Andrea Merenda; Weonjung Sohn; Django Seccombe; Sherub Phuntsho; Ho Kyong Shon (Process Safety and Environmental Protection, 2026)

Taixinan contourite and mixed systems on the Gaoping Slope: Influence of intermediate water masses on the Taixinan canyon group - Zhi Lin Ng; Shan Liu; Kunwen Luo; Xinyu Xue; Zhixuan Lin; Tzu-Ting Chen; Ho-Han Hsu; Ming Su (Quaternary Science Reviews, 2026)

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Synthesis and production of hydroxytyrosol derivatives with potent anti-inflammatory activities - Te-Sheng Chang; Wen-Yueh Ho; Jiumn-Yih Wu; Chien-Yu Wu; Pei-Rong Cai; Bo Eng Cheong; Wilson Thau Lym Yong; Peik Lin Teoh (Natural Product Research, 2026)

Uncovering hidden β-adrenergic agonist exposure from meat consumption through nationally representative human biomonitoring in Taiwan - Ho-Tang Liao; Tzu-Hsuan Peng; Chien-Jen Wang; Jing-Fang Hsu; Ching-Chun Lin; Wen-Harn Pan; Shu-Lih Chia; Pau-Chung Chen (International Journal of Hygiene and Environmental Health, 2026)

Associations between non-methane volatile organic compounds and cause-specific mortality across 14 major categories - Shengtao Wei; Ge Chen; Lan Chen; Zijun Yang; Fei Tian; Peng Hu; Kin Fai Ho; Shanshan Ran; Dashan Zheng; Hualiang Lin (Environmental Pollution, 2026)

Valorization of baghouse dust from lime industry through carbonation processes - Hung-Chieh Liang; Cheng-You Lin; Hsing-Jung Ho; Cheng-Han Lee (Waste Management, 2026)

Applications of machine learning in enhancing evaporation estimation for small reservoirs: a case study in semi-arid South Texas - Syed Muhammad Fahad Abdullah; Chu-Lin Cheng; Jude Benavides; Jungseok Ho; Rafael M. Almeida (Modeling Earth Systems and Environment, 2026)

Circadian-dependent UV-B stress responses reveal differential antioxidant and photoprotective mechanisms in Achyranthes japonica microgreens - Ye Lin Kim; Han-Sol Sim; Jae Gil Yun; Ki-Ho Son (Molecular & Cellular Toxicology, 2026)

Environmental metrics and trade-off for aeration-driven nitrogen removal in a pilot-scale hybrid membrane-aerated biofilm reactor treating low-C/N municipal wastewater - Hsin-Chieh Lin; Ting-Wei Wu; Mengshan Lee; Ho Kyong Shon; Chia-Hung Hou (Desalination, 2026)

Synergistic LiNO3/FEC modification to nonflammable LiOTf-TMP electrolyte for durable lithium metal batteries - Chun-Jern Pan; Chia-Ho Liu; Shih-Che Lin; Chun-I Lee; Chia-Hsin Wang; Bing-Joe Hwang (Chemical Engineering Journal, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

The rice cysteine protease OsEP3A promotes seedling growth and seed development and contains a nitrogen-starvation-responsive sequence - Yong Chou Lin; Shinn Jia Tzeng; Shin Lon Ho (Plant Cell Reports, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Zebrafish Model Reveals Early Electrocardiographic and Molecular Signatures of Doxorubicin-Induced Cardiotoxicity - Zih-Yin Lai; Chi-Ying Lee; Yu-Ching Chiu; Chia-Hung Lin; Chung-Chi Yang; Chia-Chia Ho; Lawrence Yu-Min Liu; Yung-Jen Chuang (Cardiovascular Toxicology, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Antioxidant and anti-aging activities of Salvia miltiorrhiza Bunge callus extracts in H2O2-induced premature senescence and chronological aging models of human dermal fibroblasts - Shinn-Zong Lin; Tzu-Kai Lin; Wei-Wen Kuo; Shih-Wen Kao; Chia-Hua Kuo; Dennis Jine-Yuan Hsieh; Yueh-Min Lin; Tsung-Jung Ho; Shang-Chuan Ng; Chih-Yang Huang (Biogerontology, 2026)

Multi-contaminants in road runoff of a compact city: Characteristics, interactions, and ecological risks - Yinghong Lin; Brigitte Helmreich; Yuen-Wa Ho; James Kar-Hei Fang; Chunling Luo; Yuhong Wang (Water Research, 2026)

A novel approach for utilizing UAV imaging and deep learning techniques for river channel measurement and flood simulation - Jen-Yu Han; Chun-Jia Huang; Yuan-Shun Chang; Yen-Cheng Lin; Hao-Che Ho (Geomorphology, 2026)

Triarylamine-based epoxy thermosets featuring bright polyelectrochromic energy-storage and energy-saving behaviors - Yu-Jen Shao; Peng-Yi Lin; Hung-Lin Ho; Hsuan-Hsi Pai; William Sun; Yu-Jie Wang; Cha-Wen Chang; Guey-Sheng Liou (Chemical Engineering Journal, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Untargeted lipidomic profiling reveals the effect of hexabromocyclododecane exposure on a branching coral - Chuan-Ho Tang; Ting-Ju Liu; Ching-Yu Lin; Hsing-Hui Li (Aquatic Toxicology, 2026)

Development of a Stereolithography 3D Printing-Based Micropatterning Method to Study Endothelial-to-Mesenchymal Transition Mechanobiology - Karina Bender; Sarah Chesley; Jay Lesny Drake; Megan Ho; Emily Lin; Kathryn Saxton; Ninava Sharma; Christina K. Tripsas; Qian Li; Jeffrey J. Hsu (Annals of Biomedical Engineering, 2026)
Endothelial-to-mesenchymal transition (EndMT) is the process of endothelial cells undergoing molecular changes that shift their phenotype from that of endothelial cells to that of mesenchymal-like cells. It is a crucial developmental process that has been implicated in various physiological and pathological conditions. EndMT has gained attention as a potential therapeutic target for cardiovascular disease processes, including atherosclerosis, myocardial fibrosis, and vascular calcification. In addition to the assessment of endothelial and mesenchymal markers, the behavioral mechanics of endothelial cells, such as migration and invasion, are often used to identify endothelial cells that have undergone EndMT. However, whether cell chirality may be another mechanobiological marker of EndMT remains unclear. In this study, we aimed to develop an accessible micropatterning platform and created a stereolithography (SLA) 3D printing-based polydimethylsiloxane (PDMS) protein-stamp fabrication platform to create customized patterns of ECM proteins to study endothelial cell chirality during EndMT. Human aortic endothelial cells (HAECs) were treated with the inflammatory cytokine tumor necrosis factor-α (TNF-α), which resulted in the downregulation of the endothelial marker ENOS3 and the upregulation of the mesenchymal markers N-cadherin and transgelin, supporting the induction of EndMT. HAECs were seeded onto fibronectin stripe micropatterns, and cell chirality was measured using custom cell-profiling software. HAECs treated with TNF-α exhibited a shift in cell orientation by approximately 18°, supporting altered cell chirality during TNF-α-induced EndMT. Our work innovates novel methods of studying EndMT by developing a flexible and cost-effective protein-stamp fabrication and image analysis pipeline. This pipeline can be used by researchers to study the endothelial cell chirality in response to EndMT induction.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Captive breeding and early development of tank-reared lyretail anthias Pseudanthias squamipinnis (Peters, 1855): Assessments of hatching success, larval survival, and ontogeny - Ting-Chan Chou; Ang Lu; Yi-Yang Lin; Cheng-Chieh Wu; Hei-Wan Wong; Ho-Fai Yik; Bo-Kai Liao; Hong-Yi Gong; Yen-Ju Pan (Aquaculture, 2026)

Active site-rich MIL-101(Fe) derived P-doped iron sulfide/carbon octahedra for oxygen evolution electrocatalysis - Ying-Jun Jhang Jian; Pin-Yan Lee; Subbiramaniyan Kubendhiran; Lu-Yin Lin; Kevin C.-W. Wu; Kuo-Chuan Ho (Journal of Environmental Chemical Engineering, 2026)

A novel antimicrobial peptide FxCy2 against Helicobacter pylori: Isolation and purification from Lactobacillus paracasei FX-6 - Bo Bi; Meng Kang; Qianru Lin; Qun Wang; Xiaoqing Li; Zhuming Ye; Chi-Tang Ho; Yong Cao (Food Research International, 2026)

Peroxymonosulfate activation by metal-free cocoa pod husk biochar for tetracycline degradation: Efficiency and embryotoxicity in zebrafish (Danio rerio) - Chang-Mao Hung; Chia-Hao Lin; Hsuan-Yi Hsu; Tzu-Chen Lo; Yi-Chen Wang; Tsai-Hsuan Ho (Environmental Research, 2026)

A monogamous male's dilemma: Managing two females and parental care in white‐faced plovers - Boya Xie; Xi Lin; Xiaotong Niu; Heiman Ho; Xinlei Liu; Xin Lan; Zitan Song; Yachang Cheng; Yang Liu (Ecology, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Seawater-conditioned cement as a viable substrate for coral larval settlement - Elizaldy Acebu Maboloc; Jason Hon-Yin Szeto; Ken Chue-Ho Yuen; Shirley Chun-Ching Wong; Juan Carlos Astudillo; Lin Cai; Lucen Hao; Shipeng Zhang; Apple Pui-Yi Chui; James Kar-Hei Fang (Regional Studies in Marine Science, 2025)

Element redistribution along the subduction interface: metasomatism between pelitic schist and ophiolitic serpentinite in the Yuli belt, eastern Taiwan - Dominikus Deka Dewangga; Chin-Ho Tsai; Hao-Yang Lee; Yoshiyuki Iizuka; Sun-Lin Chung; Wen-Yen Chang (Lithos, 2025)

Disentangling vegetation physiological responses under extreme drought in the Amazon Rainforest: A multispectral remote sensing approach with insights from ET, SIF, and VOD - Xiang Zhang; Junyi Liu; Chao Yang; Xihui Gu; Aminjon Gulakhmadov; Jiangyuan Zeng; Hongliang Ma; Zeqiang Chen; Lin Zhao; Lingtong Du; Panda Rabindra Kumar; Mahlatse Kganyago; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Chromosome-level genome assembly reveals divergent immune mechanisms in the genus Meretrix - Che-Chun Chen; Te-Hua Hsu; Hsin-Yun Lu; Sen-Lin Tang; Ying-Ning Ho (Fish & Shellfish Immunology, 2025)

Establishment of a cobia (Rachycentron canadum) gill cell line: a valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Acute skin responses to ammonia in striped catfish (Pangasianodon hypophthalmus) unveil a potential damage-buffering mechanism - Wei-Hsuan Hsiao; Shun-Yi Lin; Tsung-Lin Liu; Han-Chen Ho; Liang-Chun Wang (Fish & Shellfish Immunology, 2025)

Interplay of plasma-treated BiVO4 photoanode and CoFe metal organic frameworks enabled synergistic photoelectrochemical water splitting - Zhi-Cheng Yan; Min-Ho Lin; Chen-Hao Yeh; Pei-Lun Chen; Jun Song Chen; Po-Hsuan Hsiao; Chia-Yun Chen (Chemical Engineering Journal, 2025)

Trans-anethole enhances mesenchymal stem cell derived exosomes function to inhibit H2O2-induced rheumatoid arthritis-like inflammation in HIG-82 synovial cells - Tai-Lung Huang; Yu-Chun Chang; Wei-Wen Kuo; Shih-Wen Kao; Chia-Hua Kuo; Dennis Jine-Yuan Hsieh; Kuan-Ho Lin; Tsung-Jung Ho; Chih-Yang Huang (Molecular Biology Reports, 2025)

Integrative analysis of coral plasticity and adaptations reveals key proteins driving resilience to changes in ocean carbonate chemistry - Xiangcheng Yuan; Ellias Y. Feng; Jingtian Wang; Lei Jiang; Tao Yuan; Hui Huang; Weihua Zhou; Jack Chi-Ho Ip; Wei-Jun Cai; Senjie Lin (Marine Life Science & Technology, 2025)
Understanding how corals adapt to changes in seawater carbonate chemistry is crucial for developing effective coral conservation strategies. Research to date has mostly focused on short-term experiments, overlooking long-term evolutionary effects. Here, we investigated the link between short-term stress responses and long-term genetic adaptations in the coral species Porites pukoensis through experiments under varying CO 2 and alkalinity conditions. Our results showed that alkalinity enrichment significantly increased coral calcification rates by 35%-45% compared to high CO 2 treatment, highlighting the potential of alkalinity enrichment to mitigate acidification impacts. Corals modulated relative expression levels of basic and acidic proteins in response to changes in seawater carbonate chemistry in the stress experiments. Genomic data revealed that this mechanism has been evolutionarily fixed in various organisms adapting to seawater carbonate chemistry. Additionally, both experimental and genomic results showed that extracellular matrix proteins, like collagen with von Willebrand factor type A domain, were modified in response to distinct carbonate environments. Molecular dynamics simulations and in-vitro experiments demonstrated that the structural stability of these proteins contributes to coral resilience under acidified conditions. This study established an integrated framework combining stress experiments, multi-omics analyses, molecular simulations, and in-vitro validation to identify key proteins involved in coral adaptation to acidification.

Urinary exposure to liquid crystal monomers (LCMs) in children near e-waste recycling sites: Occurrence and implications for physical growth - Lin Peng; Bo Xie; Qingyuan Dai; Yingjie Zhang; Jian Zhang; Rongyi Kang; Hei Tsui Ho; Xijin Xu; Xia Huo; Zongwei Cai (Journal of Hazardous Materials, 2025)

Upcycling of spent media from lactic acid bacteria as a value-added application against foodborne pathogens in vegetable processing industries - Min Ji Jang; Ho Myeong Kim; Md Ariful Haque; Carol Sze Ki Lin; Hae Woong Park; Seockmo Ku (Chemical Engineering Journal, 2025)

Energy cycle efficiency of the EU - Tai-Yu Lin; Yung-ho Chiu; Pai-Yun Hsiao (Environment, Development and Sustainability, 2025)

Alisertib inhibits acute myeloid leukemia cell growth by inhibiting STAT3 activation - Pang-Ting Cheng; Ho Lin; Yu-Chiao Cheng; Tzu-Hung Hsiao; Pei-Pei Jhan; Jia-Rung Tsai; Mei-Chih Chen; Tai-Lin Chen; Chieh-Lin Jerry Teng (Toxicology and Applied Pharmacology, 2025)

Integrating satellite information, land use regression, and machine learning to estimate the spatiotemporal variation of ionic composition in PM2.5 across Taiwan - Kang Lo; Tang-Huang Lin; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Chun-Sheng Huang; Ho-Tang Liao; Yee-Lin Wu; Chang-Fu Wu (Science of The Total Environment, 2025)

Boosting biomass upcycling into 2,5-furandicarboxylic acid via amine-induced protonation on ternary metal-organic heterojunction - Haiqing Zhao; Tianxu Shen; Wei Ji; Jason Chun-Ho Lam; Qi Hao; Laihong Shen; Richen Lin (Chemical Engineering Journal, 2025)

Effects of lichen symbiotic bacteria-derived indole-3-acetic acid on the stress responses of an algal–fungal symbiont - Yan-Yu Lin; Han-Chen Ho; Jui-Yu Chou (Brazilian Journal of Microbiology, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Interactions of the Background State and Eddies in Shaping Aleutian Low Variations - Nan Lin; Tuantuan Zhang; Qiaoling Ren; Ho-Nam Cheung; Chang-Hoi Ho; Song Yang (Advances in Atmospheric Sciences, 2025)

Ambient air pollution exposure accelerates the occurrence of 78 non-communicable chronic diseases: an accelerated failure time analysis of a nationwide cohort - Fei Tian; Shengtao Wei; Zhengmin Qian; Jinde Zhao; Yuhua Wang; Kin-fai Ho; Lauren D. Arnold; Tom Burroughs; Hualiang Lin (GeroScience, 2025)

Reconstructed vanadium carbide MXene supported cerium based trimetallic phosphide as an efficient electrocatalyst for alkaline water splitting - Yu-Han Pan; Sakthivel Perumal; Mani Sakthivel; Shan-Ni Lin; Min-Hsin Yeh; Wen-Yueh Yu; Kuo-Chuan Ho (Chemical Engineering Journal, 2025)

Mitigating non-point source pollution in tea plantations: SWAT modeling and field validation of slow-release fertilizers - Chia-Chun Ho; Pin-Chih Shih; Li-Chi Chiang; Yi-Xuan Lin; Hsiu-Feng Liu; Wen-Guei Chang; Guan-Zhou Lin (Environmental Monitoring and Assessment, 2025)

Facile synthesis of trimetallic compounds based on cobalt and nickel with ammonium fluoride-based complex for energy storage applications - Tsai-Mu Cheng; Pei-Chen Kuo; Yi-Chun Lai; Pin-Yan Lee; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Kuo-Chuan Ho; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Effects of bulk-rock chemistry on paragonite stability in high-pressure epidote-amphibolites from the Yuli metamorphic belt, Taiwan - Wen-Han Lo; Chin-Ho Tsai; Ioannis Baziotis; Sun-Lin Chung; Chiao Liu; Yoshiyuki Iizuka; Hao-Yang Lee (Contributions to Mineralogy and Petrology, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Origin and metamorphism of ophiolitic serpentinites from the Yuli belt, eastern Taiwan: new findings and tectonic implications - Dominikus Deka Dewangga; Chin-Ho Tsai; Yoshiyuki Iizuka; Ilona Talvikki Sakaguchi; Yui Kouketsu; Sun-Lin Chung; Chi-Yu Lee; Wen-Yen Chang; Huei-Fen Chen (International Geology Review, 2025)

Coral incorporating microplastics leads to a health-risking immunometabolic shift - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li (Chemosphere, 2025)

Knockout of dead end 1 by CRISPR/Cas9 leads to loss of germ cells and male-biased sex development in freshwater angelfish (Pterophyllum scalare) - Wai-Kwan Chu; Shih-Chin Huang; Ching-Fong Chang; Yu-Ho Lin; Jen-Leih Wu; Hong-Yi Gong (Aquaculture, 2025)

Evaluating European countries' progress towards SDGs: Insights from parallel SBM DEA analysis of economic, healthcare, environmental, and educational efficiencies - Tai-Yu Lin; Yung-Ho Chiu; Jia Sheng Lu; Liang-Chun Lu; Hsiu-Fang Chien (Journal of Environmental Management, 2025)

Sustainable high-performance density—nanoporous composite wood for water evaporation-induced electricity generation - Man Yi Wong; Abhishek Gautam; Kaixin Lin; Jianheng Chen; Tsz Chung Ho; Muhammad Fahim; Xu Chen; Aiqiang Pan; Chi Yan Tso (Chemical Engineering Journal, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

Groundwater Level Prediction by Wavelet Deep Learning with Smart Pumping Data - Tsai-Ning Weng; Ray-Shyan Wu; Tzu-Han Weng; Yi-Ho Chen; Tsai-Chun Lai; Jui-Yun Hsieh; Chu-Chun Hsu; Yuan-Chien Lin (Water Resources Management, 2025)

A special lycopene ε-cyclase from Chromochloris zofingiensis ATCC 30412 with multiple catalytic functions - Xing Meng; Xi Li; Ruijuan Ma; Wenjin Lin; Yiping Zou; Baobei Wang; Shih-Hsin Ho; Jianfeng Chen; Youping Xie (Algal Research, 2025)

Chlorophyll-deficient triggers heterotrophic lutein-directed biosynthesis in a novel mutant strain of Chlorella sorokiniana (Chlorophyta): Process characterization and underlying mechanism - Youping Xie; Wenjin Lin; Wen Zhang; Xing Meng; Ruijuan Ma; Baobei Wang; Shih-Hsin Ho; Jianfeng Chen; Jo-Shu Chang (Aquaculture, 2025)

Integrative multi-omics analysis of metabolic dysregulation induced by occupational benzene exposure in mice - Sydney Scofield; Lisa Koshko; Lukas Stilgenbauer; Alix Booms; Roxanne Berube; Christopher Kassotis; Chung-Ho Lin; Hyejeong Jang; Seongho Kim; Paul Stemmer; Adelheid Lempradl; Marianna Sadagurski (Science of The Total Environment, 2025)

Unveiling secondary inorganic PM2.5 pollution in northern Taiwan: The role of aerosol acidity and transformation processes - Ankita Katoch; Chi-Chi Lin; Yu-Chieh Ting; Thi Phuong Thao Ho; Kuan-Ting Liu; Atar Singh Pipal; Yu-Hsiang Cheng (Science of The Total Environment, 2025)

Spatiotemporal variation in marine plankton communities driven by environmental changes in the East China sea - Chia-Ting Chen; Pei-Chi Ho; Fan-Sian Lin; Esther Wong; Fuh-Kwo Shiah; Gwo-Ching Gong; Chih-hao Hsieh (Progress in Oceanography, 2025)

The plant retromer components SNXs bind to ATG8 and CLASP to mediate autophagosome movement along microtubules - Yanglan Liao; Xibao Li; Wenlong Ma; Xinyi Lin; Jiayi Kuang; Xuanang Zheng; Zien Li; Fanfan Qiao; Chuanliang Liu; Jun Zhou; Faqiang Li; Ruixi Li; et al. (Molecular Plant, 2025)

Analyzing the influence of pore structure and vibration on clogging in pervious concrete - Wuguang Lin; Lin Liu; Han Ye; Qifeng Yu; Yoon-Ho Cho (Journal of Cleaner Production, 2025)

An injectable in situ-forming hydrogel with self-activating genipin-chitosan (GpCS) cross-linking and an O2/Ca2+ self-supplying capability for wound healing and rapid hemostasis - Chi Lin; Tzu-Wei Lu; Fang-Yu Hsu; Tzu-Wen Huang; Ming-Hua Ho; Hsien-Tsung Lu; Fwu-Long Mi (Carbohydrate Polymers, 2025)

A new species of Hoplostethus from Sumatra , eastern Indian Ocean , with comments on its most similar congeners ( Trachichthyiformes : Trachichthyidae ) - Yo Su; Alexander N. Kotlyar; Hsiu‐Chin Lin; Toshio Kawai; Hsuan‐Ching Ho (Journal of Fish Biology, 2025)
A new species of the roughy fish genus Hoplostethus , subgenus Leiogaster , is described based on three specimens collected from Sumatra, Indonesia. This species can be distinguished from its congeners by the following characteristics: gular region covered with ctenoid scales; pelvic‐fin spine smooth on its anterior edge; head depth subequal or smaller than its length (37.2%–38.6% standard length [SL], or 94.7%–99.2% head length [HL]); pectoral‐fin length 35.6%–37.8% SL, reaching beyond a vertical through anal‐fin origin; abdominal scutes well developed, 12–16; pectoral‐fin rays uniformly black, 17–19; gill rakers on the first arch 6–7 + 1 + 13–14 = 21; pre‐dorsal scales 24–27; and pyloric caeca 32. A detailed description is provided along with comparisons with its congeners. Additionally, diagnostic characters of the congeners and literature records of Hoplostethus rubellopterus and Hoplostethus melanopus are discussed.

High performance catalyst CoNP for efficient electrochemical production of hydrogen peroxide - Ko-Shan Ho; Kuan-Ying Hung; Yu-Lin Hsiao; Hsiu-Chung Tu (Journal of Environmental Chemical Engineering, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Year-round natural spawning, early ontogeny, and larval rearing of the painted sweetlips, Diagramma pictum (Thunberg, 1792) in a hatchery: Potential as a new species for mariculture - Pei-Sheng Chiu; Bo-Hong Yu; Yu-Hsin Tu; Yeong-Torng Chu; Cheng-Hsuan Huang; Shine-Wei Ho; Sun-Hon Lin; Shinn-Lih Yeh; Ming-Yih Leu (Aquaculture, 2025)

High spatial–temporal image fusion model for retrieving aerosol optical depth based on top-of-atmosphere reflectance - Chih-Yuan Huang; Hsuan-Chi Ho; Tang-Huang Lin (Remote Sensing Applications: Society and Environment, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

The Palomar twilight survey of ‘Ayló’chaxnim, Atiras, and comets - B.T. Bolin; F.J. Masci; M.W. Coughlin; D.A. Duev; Ž. Ivezić; R.L. Jones; P. Yoachim; T. Ahumada; V. Bhalerao; H. Choudhary; C. Contreras; Y.-C. Cheng; et al. (Icarus, 2025)

Determinants of soundscape quality of communal open space in Hong Kong - Minqi LIN; Chi Kwan CHAU; Shiu Keung TANG; Wai Kit CHUNG; Ho Man YU (Building and Environment, 2025)

Characterization and ecological risks of microplastics in urban road runoff - Yinghong Lin; Yuhong Wang; Yuen-Wa Ho; James Kar-Hei Fang; Yuan Li (Science of The Total Environment, 2024)

The effects of corona discharge from a cold plasma source on the physicochemical properties and shelf-life of milk - Tan-Ang Lee; Yi-Hsuan Lin; Po-Hsien Li; Jou-Hsuan Ho (Food Bioscience, 2024)

The association of air pollution with blood pressure, heart rate and stress among office workers using essential oils - Chien-Yu Lee; I-Jung Liu; Chih-Hong Pan; Lian-Yu Lin; Hsiao-Chi Chuang; Kin-Fai Ho; Chia-Huang Chang; Kai-Jen Chuang (Atmospheric Environment, 2024)

Evaluating the embryotoxicity of benzophenone-based photoinitiators in stem cells and zebrafish embryos - Chen-Yi Weng; Tzu-Ching Chang; Jun-Yang Liou; Ju-Hsin Hsu; Chia-Chi Ho; Salim Arrokhman; Pinpin Lin (Toxicology, 2024)

Revealing the hidden resource of fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae): Asteraceae weeds as alternative hosts - Yun Hsiao; Feng-Chuan Hsu; You-Ting Hsieh; Wei-Jiun Lin; Xun-Yi Huang; Chuan-Kai Ho (Applied Entomology and Zoology, 2024)

Screening and rational identification of a novel angiotensin-converting enzyme C-domain inhibitory peptide from Fabaceae food peptide library - Tin-Yun Ho; Hsin-Yi Lo; Guan-Ling Lu; Chia-Yu Lin; Mei-Li Stevens; Chiao-Che Chen; Chien-Yun Hsiang (Food Chemistry, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Natural coral recovery despite negative population growth - Aziz J. Mulla; Vianney Denis; Che‐Hung Lin; Chia‐Ling Fong; Jia‐Ho Shiu; Yoko Nozawa (Ecology, 2024)
Demographic processes that ensure the recovery and resilience of marine populations are critical as climate change sends an increasing proportion on a trajectory of decline. Yet for some populations, recovery potential remains high. We conducted annual monitoring over 9 years (2012–2020) to assess the recovery of coral populations belonging to the genus Pocillopora . These populations experienced a catastrophic collapse following a severe typhoon in 2009. From the start of the monitoring period, high initial recruitment led to the establishment of a juvenile population that rapidly transitioned to sexually mature adults, which dominated the population within 6 years after the disturbance. As a result, coral cover increased from 1.1% to 20.2% during this time. To identify key demographic drivers of recovery and population growth rates (λ), we applied kernel‐resampled integral projection models (IPMs), constructing eight successive models to examine annual change. IPMs were able to capture reproductive traits as key demographic drivers over the initial 3 years, while individual growth was a continuous key demographic driver throughout the entire monitoring period. IPMs further detected a pulse of reproductive output subsequent to two further Category 5 typhoon events during the monitoring period, exemplifying key mechanisms of resilience for coral populations impacted by disturbance. Despite rapid recovery, (i.e., increased coral cover, individual colony growth, low mortality), IPMs estimated predominantly negative values of λ, indicating a declining population. Indeed, while λ translates to a change in the number of individuals, the recovery of coral populations can also be driven by an increase in the size of surviving colonies. Our results illustrate that accumulating long‐term data on historical dynamics and applying IPMs to extract demographic drivers are crucial for future predictions that are based on comprehensive and robust understandings of ecological change.

The different adsorption-degradation behaviors of SARS-CoV-2 by bioactive chemicals in wastewater: The suppression kinetics and their implications for wastewater-based epidemiology - Mohamed Bayati; Hsin-Yeh Hsieh; Shu-Yu Hsu; Sally Qasim; Chenhui Li; Anthony Belenchia; Jessica Klutts; Sally A. Zemmer; Kristen Sibley; Melissa Reynolds; Elizabeth Semkiw; Hwei-Yiing Johnson; et al. (Science of The Total Environment, 2024)

Solar-driven adaptive radiative cooling coating with polymer carbon dots-enhanced photoluminescence for urban skin - Quan Gong; Ho Chun Wong; Jianheng Chen; Pei Li; Lin Lu (Chemical Engineering Journal, 2024)

Retraction Note: Role of energy consumption and sustainability-oriented eco-innovation on economic growth: evidence from Middle Eastern economy - Yu-Te Tu; Chia-Yang Lin; Syed Ehsanullah; Nguyen Ho Viet Anh; Khoa Dang Duong; Pham Quang Huy (Environmental Science and Pollution Research, 2024)

Functional identification of specialized diterpene synthases from Chamaecyparis obtusa and C. obtusa var. formosana to illustrate the putative evolution of diterpene synthases in Cupressaceae - Tsai-Jung Wu; Chi-Chun Lin; Li-Ting Ma; Chih-Kai Yang; Chen-Lung Ho; Sheng-Yang Wang; Fang-Hua Chu (Plant Science, 2024)

Beyond just green: Explaining and predicting restorative potential of urban landscapes using panorama-based metrics - Xudong Zhang; Ervine Shengwei Lin; Puay Yok Tan; Jinda Qi; Roger Ho; Angelia Sia; Radha Waykool; Xiao Ping Song; Agnieszka Olszewska-Guizzo; Lingshuang Meng; Yue Cao (Landscape and Urban Planning, 2024)

The joint effect of long-term exposure to multiple air pollutants on non-accidental and cause-specific mortality: A longitudinal cohort study - Xianglin Wei; Kin Fai Ho; Tsung Yu; Changqing Lin; Ly-yun Chang; Dezhong Chen; Tony Tam; Bo Huang; Alexis K.H. Lau; Xiang Qian Lao (Journal of Hazardous Materials, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Environmental evaluation of emerging bakery waste oil-derived sophorolipids production by performing a dynamic life cycle assessment - Yahui Miao; Xiaomeng Hu; Ming Ho To; Huaimin Wang; Zihao Qin; Jinhua Mou; Wei Yan; Guneet Kaur; Sophie L.K.W. Roelants; Carol Sze Ki Lin; Shauhrat S. Chopra (Sustainable Production and Consumption, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Correction: Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)

Numerical seismic performance assessment and fragility analysis for gravity-type wharves considering the influence of soil liquefaction - Yung-Yen Ko; Ho-Hsiung Yang; Chi-Wen Hu; Yan-Jhih Huang; Yu-Ying Lin (Soil Dynamics and Earthquake Engineering, 2024)

Establishment of a cobia (Rachycentron canadum) gill cell line: A valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

Towards healthy cities: Modeling restorative potential of urban environments by coupling LiDAR-derived 3D metrics with panorama-based online survey - Xudong Zhang; Jinda Qi; Ervine Shengwei Lin; Puay Yok Tan; Roger Ho; Angelia Sia; Xiao Ping Song; Radha Waykool; Agnieszka Olszewska-Guizzo (Environmental Impact Assessment Review, 2024)

Multi-functional hydrogen- and oxygen-capturing FeCo-N-C catalyst with improved hydrogenation of nitroarenes and ORR activity - Hsiu-Chung Tu; Yu-Lin Hsiao; Yi-Dong Lin; Yan-Gu Lin; Ding-Liang Liao; Ko-Shan Ho (Chemical Engineering Journal, 2024)

Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)
Bacteria with functional DNA repair systems are expected to have low mutation rates due to strong natural selection for genomic stability. However, our study of the wild-type Streptococcus pneumoniae D39, a pathogen responsible for many common diseases, revealed a high spontaneous mutation rate of 0.02 per genome per cell division in mutation-accumulation (MA) lines. This rate is orders of magnitude higher than that of other non-mutator bacteria and is characterized by a high mutation bias in the A/T direction. The high mutation rate may have resulted from a reduction in the overall efficiency of selection, conferred by the tiny effective population size in nature. In line with this, S. pneumoniae D39 also exhibited the lowest DNA mismatch-repair (MMR) efficiency among bacteria. Treatment with the antibiotic penicillin did not elevate the mutation rate, as penicillin did not induce DNA damage and S. pneumoniae lacks a stress response pathway. Our findings suggested that the MA results are applicable to within-host scenarios and provide insights into pathogen evolution.

Comparative analysis of Deinagkistrodon acutus venom from Taiwan and China utilizing chromatographic, electrophoretic, and bioinformatic approaches, along with ELISA employing a monospecific antivenom - Tein-Shun Tsai; Inn-Ho Tsai; Jing-Lin Qiu; Yuen-Ying Chan; Yu-Wei Chiang (Toxicon, 2024)

Dinaciclib inhibits the growth of acute myeloid leukemia cells through either cell cycle-related or ERK1/STAT3/MYC pathways - Chieh-Lin Jerry Teng; Pang-Ting Cheng; Yu-Chiao Cheng; Jia-Rung Tsai; Mei-Chih Chen; Ho Lin (Toxicology in Vitro, 2024)

Flushing emissions of methane and carbon dioxide from mangrove soils during tidal cycles - Chiao-Wen Lin; Wei-Jen Lin; Chuan-Wen Ho; Yu-Chen Kao; Zhao-Jun Yong; Hsing-Juh Lin (Science of The Total Environment, 2024)

Exposure to BTEX is associated with cardiovascular disease, dyslipidemia and leukocytosis in national US population - Yansu He; Hong Qiu; Wenqiao Wang; Yong Lin; Kin Fai Ho (Science of The Total Environment, 2024)

Weakening the integrity of waxy starch granules by selective degradation of amorphous matrices using gaseous hydrogen chloride - Chia-Long Lin; Jheng-Hua Lin; Ciao-Ling Pan; Yung-Ho Chang (Carbohydrate Polymers, 2024)

Population parameters and heterogeneity in survival rates of Indo-Pacific humpback dolphins in a heavily urbanized coastal region of southeast China: implications for conservation - Wenzhi Lin; Leszek Karczmarski; Stephen C. Y. Chan; Ruiqiang Zheng; Yuen-Wa Ho; Yaqian Mo (Frontiers in Marine Science, 2024)
The Pearl River Delta (PRD) region on the southeast coast of China is among the largest and most populated metropolitan regions of the world, subjecting the Indo-Pacific humpback dolphins ( Sousa chinensis ) inhabiting coastal waters of this region – apparently the largest population of this species – to intense anthropogenic pressure. In this 5-year study (2011-2015), we applied mark-recapture techniques to quantify population parameters of humpback dolphins in the main body of the extensive estuarine system of the Pearl River, the Lingding Bay (LB), the most urbanized and industrialized part of PRD. The super-population size was estimated at 928 individuals (95% CI=823-1046), which however over-represents the latest number of extant animals. Annual estimates fluctuated between 708 and 750 dolphins, and likely reflect most accurately the latest/current number of humpback dolphins in waters of LB. Both the overall and annual estimates generated by our study are considerably lower than previously published abundance estimates. Apparent survival rates were generally low, estimated at 0.943 (SE = 0.008, 95% CI = 0.929-0.958) and 0.815 (SE = 0.025, 95% CI = 0.766-0.866) for adults and juveniles, respectively. In conjunction with limited recruitment, they may have led to a substantial decline in population numbers over the past two decades. Notably, dolphins exhibited heterogeneous apparent survival rates across the complex anthropogenic seascape of LB. Adult individuals that use Hong Kong waters as their primary habitat exhibited 6.2% higher survival rates than those in other parts of LB. This difference tripled (19.2%) for juveniles, a likely expression of their susceptibility to environmental and/or anthropogenic stresses. We suggest that the difference in survival is largely due to heterogeneous anthropogenic stressors that vary spatially across the estuary, among which habitat loss, pollution, and declining prey resources appear to be the primary threats. Based on our latest findings, we call for a strategic conservation planning with the highest priority given to preserve the remaining key dolphin habitats in Hong Kong waters, and to quantify and mitigate the impacts of major stressor(s) in Guangdong (mainland China) waters. Given the encroachment of ever-more-intense human activities on the coastal habitats of humpback dolphins, understanding their demographic response and the underlying mechanisms of the population processes may prove instrumental in the formulation of a conservation management strategy that can secure their continuous survival.

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

A novel packing-coupled stress-strain model for confined concrete - M.H. Lai; J.L. Lin; J. Cui; F.M. Ren; S. Kitipornchai; J.C.M. Ho (Engineering Structures, 2024)

A memory-rich conjugated microporous polymer-based electrochromic framework through two-in-one metal catalyst free route - Gaurav Kumar Silori; Szu-Chia Chien; Li-Chiang Lin; Kuo-Chuan Ho (Chemical Engineering Journal, 2024)

Impact assessment of spatial–temporal distribution of riverine dust on air quality using remote sensing data and numerical modeling - Ho-Wen Chen; Chien-Yuan Chen; Guan-Yu Lin (Environmental Science and Pollution Research, 2024)

Single-cell lineage tracing with endogenous markers - Yan Xue; Zezhuo Su; Xinyi Lin; Mun Kay Ho; Ken H. O. Yu (Biophysical Reviews, 2024)
Resolving lineage relationships between cells in an organism provides key insights into the fate of individual cells and drives a fundamental understanding of the process of development and disease. A recent rapid increase in experimental and computational advances for detecting naturally occurring somatic nuclear and mitochondrial mutation at single-cell resolution has expanded lineage tracing from model organisms to humans. This review discusses the advantages and challenges of experimental and computational techniques for cell lineage tracing using somatic mutation as endogenous DNA barcodes to decipher the relationships between cells during development and tumour evolution. We outlook the advantages of spatial clonal evolution analysis and single-cell lineage tracing using endogenous genetic markers.

Linkage analysis for water-energy-economic system efficiency in China - Zhong Fang; Yung-ho Chiu; Yiqin Chen; Tai-Yu Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2024)

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Microplastics elicit an immune-agitative state in coral - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li; Fu-Wen Kuo (Science of The Total Environment, 2024)

Interaction among local flows, UHI, coastal winds, and complex terrain: Effect on urban-scale temperature and building energy consumption during heatwaves - Ruiqing Du; Chun-Ho Liu; Xianxiang Li; Chuan-Yao Lin (Energy and Buildings, 2024)

Representing the landscape visual quality of residential green spaces in Singapore with 3D spatial metrics - Jinda Qi; Ervine Shengwei Lin; Puay Yok Tan; Xudong Zhang; Roger Ho; Angelia Sia; Agnieszka Olszewska-Guizzo; Radha Waykool (Urban Forestry & Urban Greening, 2023)

The joint association of ambient air pollution and different sleep posture with mild obstructive sleep apnea: A study conducted at Taipei Sleep Center - Yansu He; Wen-Te Liu; Shangyang Lin; Zhiyuan Li; Hong Qiu; Steve Hung Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

The Pacific water flow branches in the eastern Chukchi Sea - Robert S. Pickart; Peigen Lin; Frank Bahr; Leah T. McRaven; Jie Huang; Astrid Pacini; Kevin R. Arrigo; Carin J. Ashjian; Catherine Berchok; Mark F. Baumgartner; Kyoung-Ho Cho; Lee W. Cooper; et al. (Progress in Oceanography, 2023)

Intrinsic and extrinsic factors influencing Populus water use: A literature review - Elizabeth R. Rogers; Ronald S. Zalesny; Chung-Ho Lin; Ryan A. Vinhal (Journal of Environmental Management, 2023)

Application of novel nanobubble-contained electrolyzed catalytic water to cleanup petroleum-hydrocarbon contaminated soils and groundwater: A pilot-scale and performance evaluation study - Wing-Sze Ho; Wei-Han Lin; Francis Verpoort; Kun-Liang Hong; Jiun-Hau Ou; Chih-Ming Kao (Journal of Environmental Management, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Intensity change and zonal and meridional movements of the Aleutian Low and their associated broad-scale atmospheric-oceanic characteristics - Nan Lin; Song Yang; Qiaoling Ren; Tuantuan Zhang; Ho-Nam Cheung (Atmospheric Research, 2023)

Nuts and berries from agroforestry systems in temperate regions can form the foundation for a healthier human diet and improved outcomes from diet-related diseases - Sarah Taylor Lovell; Kiruba Krishnaswamy; Chung-Ho Lin; Nicholas Meier; Ronald S. Revord; Andrew L. Thomas (Agroforestry Systems, 2023)
Agroforestry is a specific type of agroecosystem that includes trees and shrubs with the potential to yield nutrient-rich products that contribute to human health. This paper reviews the literature on the human health benefits of tree nut and berry species commonly associated with agroforestry systems of the United States, considering their potential for preventing certain diet-related diseases. Emphasis is placed on those diseases that are most closely associated with poor outcomes from COVID-19, as they are indicators of confounding health prognoses. Results indicate that tree nuts reduce the risk of coronary heart disease, and walnuts ( Juglans species) are particularly effective because of their unique fatty acid profile. Berries that are grown on shrubs have the potential to contribute to mitigation of hypertension, prevention of Type II diabetes, and reduced risk of cardiovascular disease. To optimize human health benefits, plant breeding programs can focus on the traits that enhance the naturally-occurring phytochemicals, through biofortification. Value-added processing techniques should be selected and employed to preserve the phytonutrients, so they are maintained through the point of consumption. Agroforestry systems can offer valuable human health outcomes for common diet-related diseases, in addition to providing many environmental benefits, particularly if they are purposefully designed with that goal in mind. The food system policies in the U.S. might be reoriented to prioritize these food production systems based on the health benefits.

Agricultural production efficiency, food consumption, and food waste in the European countries - Tai-Yu Lin; Shih-Yung Chiu; Yung-ho Chiu; Liang-Chun Lu; Kuei-Ying Huang (Environment, Development and Sustainability, 2023)

Sensory-directed isolation and identification of an intense salicin-like bitter compound in infected teas with bird’s eye spot disease - Jingna Yan; Yiwen Miao; Jingyun Zhou; Rui Huang; Hongwei Dai; Ming Liu; Yunzhi Lin; Yingjuan Chen; Chi-Tang Ho; Huarong Tong; Qing Meng (Food Research International, 2023)

Quantifying the potential effects of air pollution reduction on population health and health expenditure in Taiwan - Yi-Hsuan Roger Chen; Wan-Chen Lee; Bo-Chen Liu; Po-Chieh Yang; Chi-Chang Ho; Jing-Shiang Hwang; Tzu-Hsuan Huang; Hsien-Ho Lin; Wei-Cheng Lo (Environmental Pollution, 2023)

Stochastic optimal control of mesostructure of supramolecular assemblies using dissipative particle dynamics and dynamic programming with experimental validation - Silabrata Pahari; Yu-Ting Lin; Shuhao Liu; Chi Ho Lee; Mustafa Akbulut; Joseph Sang-Il Kwon (Chemical Engineering Journal, 2023)

The NOx-O3 photochemical reactive air pollutant dispersion around an isolated building—the role of turbulence model and building aspect ratio - Yunfei Fu; Xisheng Lin; Lu Li; Mengyuan Chu; Chun-Ho Liu; Zengshun Chen; Cruz Y. Li; K.T. Tse (Building and Environment, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Using drone soundings to study the impacts and compositions of plumes from a gigantic coal-fired power plant - Yen-Chen Chen; Jia-Lin Wang; Chih-Yuan Chang; Ming-Tung Chuang; Charles C.-K. Chou; Xiang-Xu Pan; Yu-Jui Ho; Chang-Feng Ou-Yang; Wen-Tzu Liu; Chih-Chung Chang (Science of The Total Environment, 2023)

Construction and demolition waste as a high-efficiency advanced process for organic pollutant degradation in Fenton-like reaction to approach circular economy - Kuan-Ting Lee; Kuan-Yu Ho; Wei-Hsin Chen; Eilhann E. Kwon; Kun-Yi Andrew Lin; Shuenn-Ren Liou (Environmental Pollution, 2023)

Design and development of a new lead-free BiFeO3-BaTiO3 quenched ceramics for high piezoelectric strain performance - Muhammad Habib; Lin Tang; Guoliang Xue; Attaur Rahman; Myong-Ho Kim; Soonil Lee; Xuefan Zhou; Yan Zhang; Dou Zhang (Chemical Engineering Journal, 2023)

Developing a survival probability-based Lagrangian model for predicting ultraviolet disinfection of bioaerosols in enclosed environments - Yue Pan; Kangqi Guo; Chao-Hsin Lin; Daniel Wei; Kin-Fai Ho; Chun Chen (Building and Environment, 2023)

Spatial-temporal evaluation of PM2.5 concentration for health risk reduction strategy development in a basin with different weather patterns - Ho-Wen Chen; Chien-Yuan Chen; Teng-Wei Chang; Guan-Yu Lin (Atmospheric Pollution Research, 2023)

Activation of MG53 Enhances Cell Survival and Engraftment of Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes in Injured Hearts - Ki Ho Park; Xingyu He; Lin Jiang; Hua Zhu; Jialiang Liang; Yigang Wang; Jianjie Ma (Stem Cell Reviews and Reports, 2023)
Background and Objective Our previous studies demonstrated that MG53 protein can protect the myocardium, but its use as a therapeutic is challenging due to its short half-life in blood circulation. This study aimed to investigate the cardioprotective role of MG53 on human induced pluripotent stem cell-derived cardiomyocytes (HiPSC-CMs) in the context of myocardial ischemia/reperfusion (I/R). Methods In vitro : HiPSC-CMs were transfected with adenoviral MG53 (HiPSC-CMs MG53 ), in which the expression of MG53 can be controlled by doxycycline (Dox), and the cells were then exposed to H 2 O 2 to mimic ischemia/reperfusion injury. In vivo : HiPSC-CMs MG53 were transplanted into the peri-infarct region in NSG™ mice after I/R. After surgery, mice were treated with Dox (+ Dox) to activate MG53 expression (sucrose as a control of -Dox) and then assessed by echocardiography and immunohistochemistry. Results MG53 can be expressed in HiPSC-CM MG53 and released into the culture medium after adding Dox. The cell survival rate of HiPSC-CM MG53 was improved by Dox under the H 2 O 2 condition. After 14 and 28 days of ischemia/reperfusion (I/R), transplanted HiPSC-CMs MG53 + Dox significantly improved heart function, including ejection fraction (EF) and fractional shortening (FS) in mice, compared to HiPSC-CMs MG53 -Dox, and reduced the size of the infarction. Additionally, HiPSC-CM MG53 + Dox mice demonstrated significant engraftment in the myocardium as shown by staining human nuclei-positive cells. In addition, the cell survival-related AKT signaling was found to be more active in HiPSC-CM MG53 + Dox transplanted mice’s myocardium compared to the HiPSC-CM MG53 -Dox group. Notably, the Dox treatment did not cause harm to other organs. Conclusion Inducible MG53 expression is a promising approach to enhance cell survival and engraftment of HiPSC-CMs for cardiac repair. Graphical Abstract

Neuroprotective Effects of Probiotic Lactobacillus reuteri GMNL-263 in the Hippocampus of Streptozotocin-Induced Diabetic Rats - Jing-Ying Lin; Bruce Chi-Kang Tsai; Hui-Chuan Kao; Chien-Yi Chiang; Yun-An Chen; William Shao-Tsu Chen; Tsung-Jung Ho; Chun-Hsu Yao; Wei-Wen Kuo; Chih-Yang Huang (Probiotics and Antimicrobial Proteins, 2023)

Profit-seeking enterprise production and business waste treatment efficiency in Taiwan - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2023)

New depth record for oval squid, Sepioteuthis lessoniana, egg capsules in a mesophotic coral ecosystem natural habitat - Chao-Yang Kuo; Chun-Yen Lin; Ming-Jay Ho; Chaolun Allen Chen (Marine Biodiversity, 2023)

Simultaneous removal of sulfamethoxazole during fermentative production of short-chain fatty acids - Yue Wang; Rongrong Lin; Yushuang Cao; Shuangfei Li; Rong Cui; Wanqian Guo; Shih-Hsin Ho; Yoong Kit Leong; Duu-Jong Lee; Jo-Shu Chang (Bioresource Technology, 2023)

Dynamic total factors’ environmental efficiency in European union countries - Ching-Cheng Lu; Yung-ho Chiu; I-Fang Lin; Tai-Yu Lin (Environment, Development and Sustainability, 2023)

Air pollution exacerbates mild obstructive sleep apnea by disrupting nocturnal changes in lower-limb body composition: a cross-sectional study conducted in urban northern Taiwan - Yansu He; Wen-Te Liu; Shang-Yang Lin; Zhiyuan Li; Hong Qiu; Steve Hung-Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

Sustainable utilization of aging-deteriorated microplastics as triboelectric nanogenerator - Seongeun Cho; Kyunghwan Cha; Banseok Kim; Joonseok Lee; Kyungtae Park; Seh-Hoon Chung; Myunghwan Song; Deokjae Heo; Jin-ho Son; Moonhyun Choi; Zong-Hong Lin; Jinkee Hong; et al. (Chemical Engineering Journal, 2023)

Stem Cell Therapy in Spinal Cord Injury-Induced Neurogenic Lower Urinary Tract Dysfunction - Yin-Chien Ou; Chi-Chen Huang; Yao-Lin Kao; Pei-Chuan Ho; Kuen-Jer Tsai (Stem Cell Reviews and Reports, 2023)

Livistona chinensis Water Extract has the Potential to Repair Thioacetamide-Induced Liver Fibrosis in Mice - San-Ho Hung; Tzu-Hsuan Hsu; Chun-Shien Wu; Yi-Ping Lin; Ching-Ting Wei; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2023)

Captive Reproductive Behavior, Spawning, and Early Development of White-Barred Goby Amblygobius phalaena (Valenciennes, 1837) and Examined Larval Survival and Viability at Different Water Temperatures and Salinities - Pei-Sheng Chiu; Shine-Wei Ho; Cheng-Hsuan Huang; Yen-Chun Lee; Yu-Hung Lin (Fishes, 2023)
White-barred goby Amblygobius phalaena is a highly valued marine ornamental fish, but its captive reproduction and early life history are poorly understood. In this study, the captive reproductive behavior, early development, and optimal temperature and salinity for the larval survival and viability of A. phalaena were investigated for the first time. Spawning occurred between 11:00 and 13:00, with the breeding pairs naturally spawning 24 times from 1 June 2021 to 30 June 2022. The fecundity ranged from 11,022 to 95,858 eggs per spawning event. Hatching occurred approximately 81 h and 26 min after fertilization at a temperature of 27.0 ± 0.9 °C. Newly hatched larvae had a total length (TL) of 1.91–2.03 mm with 24–26 somites. The larvae transformed into juveniles at 30 days post-hatch. Experiments were conducted at different temperatures (21, 24, 27, 30, and 33 °C) and salinities (18, 24, 30, and 36 ppt) to determine the optimal conditions for larval survival and viability. The results indicate that the most suitable conditions in terms of temperature were in the range of 21–27 °C and 30 ppt for salinity. These findings provide valuable insights for the future development of captive-breeding techniques and the commercial production of other marine ornamental gobies.

Estimating the effect of increasing ambient temperature on antimicrobial resistance in China: A nationwide ecological study with the difference-in-differences approach - Weibin Li; Chaojie Liu; Hung Chak Ho; Lin Shi; Yingchao Zeng; Xinyi Yang; Haohai Xia; Wangjian Zhang; Cunrui Huang; Lianping Yang (Science of The Total Environment, 2023)

Optimal preparation of food waste to increase its utility for sophorolipid production by Starmerella bombicola - Ming Ho To; Huaimin Wang; Yahui Miao; Guneet Kaur; Sophie L.K.W. Roelants; Carol Sze Ki Lin (Bioresource Technology, 2023)

Investigating the nonlinear and non-stationary relationship between PM2.5 and air pollutants by wavelet signal analysis in central Taiwan - Shan-Non Feng; Yi-Ho Chen; Tzu-Han Weng; Yuan-Chien Lin (Environmental Geochemistry and Health, 2023)

Life cycle assessment: Sustainability of biodiesel production from black soldier fly larvae feeding on thermally pre-treated sewage sludge under a tropical country setting - Chin Seng Liew; Guo Ren Mong; Jun Wei Lim; Ratchaprapa Raksasat; Hemamalini Rawindran; Wai Hong Leong; M. Devendran Manogaran; Yee Ho Chai; Yeek Chia Ho; Anisa Ur Rahmah; Chuxia Lin; Kuan Shiong Khoo; et al. (Waste Management, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

Movement patterns and habitat use of adult giant trevally (Caranx ignobilis) in the South China Sea - Wei-Chuan Chiang; Shian-Jhong Lin; Ker-Yea Soong; Te-Yu Liao; Yu-Yun Chen; Yuan-Shing Ho; Chen-Te Tseng; Michael K. Musyl (Marine Biology, 2023)

Low-dose blood BTEX are associated with pulmonary function through changes in inflammatory markers among US adults: NHANES 2007–2012 - Yansu He; Yong Lin; Hong Qiu; Linying Wu; Kin Fai Ho (Environmental Science and Pollution Research, 2023)

Cardiac-specific overexpression of insulin-like growth factor II receptor-α interferes with the regulation of calcium homeostasis in the heart under hyperglycemic conditions - Shang-Yeh Lu; Bruce Chi-Kang Tsai; Dao Van Thao; Chin-Hu Lai; Michael Yu-Chih Chen; Wei-Wen Kuo; Chia-Hua Kuo; Kuan-Ho Lin; Dennis Jine-Yuan Hsieh; Chih-Yang Huang (Molecular Biology Reports, 2023)

Analysis of natural disasters and energy efficiency in China - Zhong Fang; Yung-ho Chiu; Tai-Yu Lin; Tzu-Han Chang; Yi-Nuo Lin (Environment, Development and Sustainability, 2023)

Extreme cooling of 12.5 °C triggered by Typhoon Fungwong (2008) - Zhe-Wen Zheng; Jia-Yi Lin; Ganesh Gopalakrishnan; Yi-Rui Chen; Doon-Jing Doong; Chung-Ru Ho; Quanan Zheng; Chau-Ron Wu; Chen-Fen Huang (Ocean Modelling, 2023)

Hydrogen generation from gasification of woody biomass upon acid mine drainage sludge as a novel catalyst under an air medium - Hoesuk Yim; Soheil Valizadeh; Sumin Pyo; Seong-Ho Jang; Chang Hyun Ko; Moonis Ali Khan; Byong-Hun Jeon; Kun-Yi Andrew Lin; Young-Kwon Park (Fuel, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Enhanced energy recovery from landfill leachate by linking light and dark bio-reactions: Underlying synergistic effects of dual microalgal interaction - Haixing Chang; Haowen Feng; Rupeng Wang; Xianming Zhang; Jinghan Wang; Chunlan Li; Yuanbo Zhang; Lin Li; Shih-Hsin Ho (Water Research, 2023)

Flow measurement in open channels using imaging techniques in conjunction with a convolutional neural network - Hao-Che Ho; Yu-Wei Chiu; Ting-Yu Chen; Yen-Cheng Lin (Journal of Hydrology, 2023)

Chemical investigations and cytotoxic effects of metabolites from Antrodia camphorata against human hepatocellular carcinoma cells - Yih-Fung Chen; Ho-Cheng Wu; Jia-Min Chang; Horng-Huey Ko; Chu-Hung Lin; Hsun-Shuo Chang (Natural Product Research, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Greenhouse gas emission indicators, energy consumption efficiency, and optimal carbon emission allowance allocation of the EU countries in 2030 - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang; Pei-Yu Lin (Gas Science and Engineering, 2023)

Automatic diagnosis of late-life depression by 3D convolutional neural networks and cross-sample Entropy analysis from resting-state fMRI - Chemin Lin; Shwu-Hua Lee; Chih-Mao Huang; Guan-Yen Chen; Wei Chang; Ho-Ling Liu; Shu-Hang Ng; Tatia Mei-Chun Lee; Shun-Chi Wu (Brain Imaging and Behavior, 2023)
Resting-state fMRI has been widely used in investigating the pathophysiology of late-life depression (LLD). Unlike the conventional linear approach, cross-sample entropy (CSE) analysis shows the nonlinear property in fMRI signals between brain regions. Moreover, recent advances in deep learning, such as convolutional neural networks (CNNs), provide a timely application for understanding LLD. Accurate and prompt diagnosis is essential in LLD; hence, this study aimed to combine CNN and CSE analysis to discriminate LLD patients and non-depressed comparison older adults based on brain resting-state fMRI signals. Seventy-seven older adults, including 49 patients and 28 comparison older adults, were included for fMRI scans. Three-dimensional CSEs with volumes corresponding to 90 seed regions of interest of each participant were developed and fed into models for disease classification and depression severity prediction. We obtained a diagnostic accuracy > 85% in the superior frontal gyrus (left dorsolateral and right orbital parts), left insula, and right middle occipital gyrus. With a mean root-mean-square error (RMSE) of 2.41, three separate models were required to predict depressive symptoms in the severe, moderate, and mild depression groups. The CSE volumes in the left inferior parietal lobule, left parahippocampal gyrus, and left postcentral gyrus performed best in each respective model. Combined complexity analysis and deep learning algorithms can classify patients with LLD from comparison older adults and predict symptom severity based on fMRI data. Such application can be utilized in precision medicine for disease detection and symptom monitoring in LLD.

Transmission of antibiotic resistance genes through mobile genetic elements in Acinetobacter baumannii and gene-transfer prevention - Jeong Ho Jeon; Kyung-Min Jang; Jung Hun Lee; Lin-Woo Kang; Sang Hee Lee (Science of The Total Environment, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Two-stage dynamic data envelopment analysis measuring the overall efficiency and productivity changes of industry and agriculture in EU countries - Ching-Cheng Lu; I-Fang Lin; Tai-Yu Lin; Yung-ho Chiu (Journal of Cleaner Production, 2023)

Molecular weight, chain length distribution and long-term retrogradation of cassava starch modified by amylomaltase - Hua-Tsung Lin; An-I Yeh; Tuan-Hua David Ho; Min-Hsiung Pan; Shih Hsin Chen (Food Hydrocolloids, 2023)

Intelligent films of marine polysaccharides and purple cauliflower extract for food packaging and spoilage monitoring - Han-Lun Huang; I-Lin Tsai; Chi Lin; Yu-Hao Hang; Yi-Cheng Ho; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Equilibrative Nucleoside Transporter 1 is a Target to Modulate Neuroinflammation and Improve Functional Recovery in Mice with Spinal Cord Injury - Kuan-Yu Chen; Chiao-Shin Lu; Cheng-Yoong Pang; Chin-Jui Ho; Kuo-Chen Wu; Hsiu-Wei Yang; Hsin-Lin Lai; Yijuang Chern; Chun-Jung Lin (Molecular Neurobiology, 2023)

Angelica dahurica attenuates melanogenesis in B16F0 cells by repressing Wnt/β-catenin signaling - Chien-Liang Fang; Debakshee Goswami; Chia-Hua Kuo; Cecilia Hsuan Day; Mei-Yi Lin; Tsung-Jung Ho; Liang-Yo Yang; Dennis Jine-Yuan Hsieh; Tzu-Kai Lin; Chih-Yang Huang (Molecular & Cellular Toxicology, 2023)

RETRACTED ARTICLE: Role of energy consumption and sustainability-oriented eco-innovation on economic growth: evidence from Middle Eastern economy - Yu-Te Tu; Chia-Yang Lin; Syed Ehsanullah; Nguyen Ho Viet Anh; Khoa Dang Duong; Pham Quang Huy (Environmental Science and Pollution Research, 2023)

Defect inspection of indoor components in buildings using deep learning object detection and augmented reality - Shun-Hsiang Hsu; Ho-Tin Hung; Yu-Qi Lin; Chia-Ming Chang (Earthquake Engineering and Engineering Vibration, 2023)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

The influence of climate change on the allocation efficiency of new and tradition energy - Kuei-Ying Huang; Yung-ho Chiu; Tzu-Han Chang; Tai-Yu Lin (Environmental Science and Pollution Research, 2022)

Groundwater vulnerability assessment of shallow aquifer in the South Texas sand sheet using a GIS-based DRASTIC model - Syed Istiyak Ahmed; Chu-Lin Cheng; Juan Gonzalez; James J. Kang; Jungseok Ho; Leslie Soto-Sanchez (Modeling Earth Systems and Environment, 2022)

Hoplostethus roseus , a new roughy fish from the western Pacific based on morphology and DNA barcoding (family Trachichthyidae) - Yo Su; Hsiu‐Chin Lin; Hsuan‐Ching Ho (Journal of Fish Biology, 2022)
A new species of the roughy fish genus Hoplostethus is described from 11 types and a non‐type specimen collected from Taiwanese waters. It can be distinguished from its congeners by a combination of characters: pectoral‐fin rays 14–17 (modally 15–16); pyloric caeca 65–84; total gill rakers 19–20; predorsal scales 18–22; oral cavity, branchial chamber, top and underside of tongue, and peritoneum uniformly black; distal margin of membrane between dorsal‐fin spines black; caudal fin without a black margin; caudal‐fin base brownish. Comparisons of the new species with similar species are provided. DNA barcoding supports the monophyly of the new species, which appears to be closely related to Hoplostethus japonicus [average cytochrome c oxidase subunit I Kimura‐2‐parameter (COI K2P) distance of 4.1%].

An unknown component of a well-known population: socio-demographic parameters of Indo-Pacific humpback dolphins (Sousa chinensis) at the western reaches of the Pearl River Delta region - Stephen C. Y. Chan; Leszek Karczmarski; Wenzhi Lin; Ruiqiang Zheng; Yuen-Wa Ho; Lang Guo; Yaqian Mo; Andy T. L. Lee; Carmen K. M. Or; Yuping Wu (Mammalian Biology, 2022)

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

Probiotics and their Metabolites Reduce Oxidative Stress in Middle-Aged Mice - Wen-Yang Lin; Jia-Hung Lin; Yi-Wei Kuo; Pei-Fang Rose Chiang; Hsieh-Hsun Ho (Current Microbiology, 2022)
Aging is an irreversible physiological degradation of living organisms. Accumulated oxidative stress and dysbiosis accelerate aging. Probiotics such as Lactobacillus and Bifidobacterium and their fermented metabolites (postbiotics) have been discovered to exhibit antioxidative activities that regulate oxidative stress and protect cells from oxidative damage. We screened selected Lactobacillus and Bifidobacterium strains and their postbiotics for potential antioxidative activity by using DPPH (2,2-Diphenyl-1-picrylhydrazyl) assay. Strains with their metabolites were selected for mixed formula in experiments involving aging mice. The aged groups presented higher oxidative stress in the brain, liver, heart, and kidney than did young mice. However, treatment with probiotic strains and their postbiotics elevated antioxidative levels, especially in the high-dose probiotics plus postbiotics group. Next-generation sequencing data revealed positive microbiota alterations of Lactobacillus and Bifidobacterium and Akkermansia in the gut. Lactobacillus johnsonii and Akkermansia muciniphila exhibited effective enlargement of relative abundance. Besides, high-dose probiotics and high-dose probiotics plus postbiotics showed significant elevation in serum SCFAs, especially in butyrate. In conclusion, the formula containing Bifidobacterium animalis subsp. infantis BLI-02, Bifidobacterium breve Bv889, Bifidobacterium bifidum VDD088, B. animalis subsp. lactis CP-9, and Lactobacillus plantarum PL-02 and their metabolites may benefit aged people’s health.

Efficient 2D multiple attenuation using SRME with curvelet-domain subtraction - Szu-Ying Lai; Yunung Nina Lin; Ho-Han Hsu (Marine Geophysical Research, 2022)
Surface Related Multiple Elimination (SRME) usually suffers the issue of either over-attenuation that damages the primaries or under-attenuation that leaves strong residual multiples. This dilemma happens commonly when SRME is combined with least-squares subtraction. Here we introduce a more sophisticated subtraction approach that facilitates better separation of multiples from primaries. Curvelet-domain subtraction transforms both the data and the multiple model into the curvelet domain, where different frequency bands (scales) and event directions (orientations) are represented by a finite number of curvelet coefficients. When combined with adaptive subtraction in the time–space domain, this method can handle model prediction errors to achieve effective subtraction. We demonstrate this method on two 2D surveys from the TAiwan Integrated GEodynamics Research (TAIGER) project. With a careful parameter determination flow, our result shows curvelet-domain subtraction outperforms least-squares subtraction in all geological settings. We also present one failed case where specific geological condition hinders proper multiple subtraction. We further demonstrate that even for data acquired with short cables, curvelet-domain subtraction can still provide better results than least-squares subtraction. We recommend this method as the standard processing flow for multi-channel seismic data.

Application of Soil and Water Assessment Tool (SWAT) to evaluate the fates of nitrogenous fertilizer in subtropical mountainous watershed tea farms - Guan-Zhou Lin; Shao-Yiu Hsu; Chia-Chun Ho; Chi-Feng Chen; Jr-Chuan Huang; Tsung-Yu Lee (Environmental Monitoring and Assessment, 2022)

Spatiotemporal distribution and the passive dispersal of fungal spores through HVAC systems - Wan-Rou Lin; Yung-Hung Ho; Wai Kwan Lee; Hsuan-Min Cheng; Pi-Han Wang (Aerobiologia, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Bacterial Communities in Coral Offspring Vary Between in situ and ex situ Spawning Environments - Jia-Ho Shiu; Che-Hung Lin; Aziz Jabir Mulla; Viet Do Hung Dang; Chia-Ling Fong; Yoko Nozawa (Frontiers in Marine Science, 2022)
Examining the bacterial communities of offspring is key to understanding the establishment of coral-bacteria associations. Although high sensitivity to the environment is expected, previous studies have only examined bacterial communities of coral offspring in ex situ (laboratory) environments, not in in situ (field) environments. Here, we examined and compared the effect of ex situ and in situ environments on bacterial communities of newly released offspring (eggs and larvae) and their maternal colonies in two phylogenetically distant coral species with different reproductive modes: Dipsastraea speciosa (Scleractinia; spawner) and Heliopora coerulea (Octocorallia; brooder). Our results demonstrated that the spawning environments do not affect the bacterial composition in maternal colonies, but influence that of the offspring (eggs of D. speciosa and larvae of H. coerulea ). Dominant bacterial operational taxonomic units (OTUs) varied between in situ and ex situ environments in the eggs of D. speciosa . The composition of bacterial communities among larvae of H. coerulea samples was more diverse in in situ environments than in ex situ environments. This study provides the first information on in situ bacterial communities in coral eggs and larvae and highlights their sensitivities to the local environment. Future studies must take into consideration the influence of ex situ environments on bacterial communities in coral offspring.

The brown root rot fungus Phellinus noxius affects microbial communities in different root‐associated niches of Ficus trees - Tse‐Yen Liu; Chao‐Han Chen; Yu‐Liang Yang; Isheng J. Tsai; Ying‐Ning Ho; Chia‐Lin Chung (Environmental Microbiology, 2022)
Summary Brown root rot (BRR) caused by Phellinus noxius is a destructive tree disease in tropical and subtropical areas. To understand how BRR affects the composition of the plant rhizoplane‐enriched microbiota, the microbiomes within five root‐associated compartments (i.e., bulk soil, old/young root rhizosphere soil, old/young root tissue) of Ficus trees naturally infected by P. noxius were investigated. The level of P. noxius infection was determined by quantitative PCR. Illumina sequencing of the internal transcribed spacer and 16S rRNA revealed that P. noxius infection caused a significant reduction in fungal diversity in the bulk soil, the old root rhizosphere soil, and the old root tissue. Interestingly, Cosmospora was the only fungal genus positively correlated with P. noxius . The abundance and composition of dominant bacterial taxa such as Actinomadura , Bacillus , Rhodoplanes , and Streptomyces differed between BRR‐diseased and healthy samples. Furthermore, 838 isolates belonging to 26 fungal and 35 bacterial genera were isolated and tested for interactions with P. noxius . Antagonistic activities were observed for isolates of Bacillus , Pseudomonas , Aspergillus , Penicillium , and Trichoderma . Cellophane overlay and cellulose/lignin utilization assays suggested that Cosmospora could tolerate the secretions of P. noxius and that the degradation of lignin by P. noxius may create suitable conditions for Cosmorpora growth.

Evaluating the energy, health efficiency, and productivity in OECD - Ching-Cheng Lu; Yung-ho Chiu; Chih-Yu Yang; Tai-Yu Lin (Environmental Geochemistry and Health, 2021)

Scleractinian diversity in the upper mesophotic zone of Ludao (Taiwan): a museum collection with new records from Taiwanese waters - Stéphane De Palmas; Vianney Denis; Derek Soto; Yuting Vicky Lin; Ming-Jay Ho; Chaolun Allen Chen (Marine Biodiversity, 2021)

Exercise renovates H2S and Nrf2-related antioxidant pathways to suppress apoptosis in the natural ageing process of male rat cortex - Jing-Ying Lin; Tsung-Jung Ho; Bruce Chi-Kang Tsai; Chien-Yi Chiang; Hui-Chuan Kao; Wei-Wen Kuo; Ray-Jade Chen; Vijaya Padma Viswanadha; Chi-Wen Huang; Chih-Yang Huang (Biogerontology, 2021)

Antifungal weapons of Lysobacter , a mighty biocontrol agent - Long Lin; Kangwen Xu; Danyu Shen; Shan‐Ho Chou; Mark Gomelsky; Guoliang Qian (Environmental Microbiology, 2021)
Summary Bacteria interact with fungi in a variety of ways to inhibit fungal growth, while the underlying mechanisms remain only partially characterized. The plant‐beneficial Bacillus and Pseudomonas species are well‐known antifungal biocontrol agents, whereas Lysobacter are far less studied. Members of Lysobacter are easy to grow in fermenters and are safe to humans, animals and plants. These environmentally ubiquitous bacteria use a diverse arsenal of weapons to prey on other microorganisms, including fungi and oomycetes. The small molecular toxins secreted by Lysobacter represent long‐range weapons effective against filamentous fungi. The secreted hydrolytic enzymes act as intermediate‐range weapons against non‐filamentous fungi. The contact‐dependent killing devices are proposed to work as short‐range weapons. We describe here the structure, biosynthetic pathway, action mode and applications of one of the best‐characterized long‐range weapons, the heat‐stable antifungal factor (HSAF) produced by Lysobacter enzymogenes . We discuss how the flagellar type III secretion system has evolved into an enzyme secretion machine for the intermediate‐range antifungal weapons. We highlight an intricate mechanism coordinating the production of the long‐range weapon, HSAF and the proposed contact‐dependent killing device, type VI secretion system. We also overview the regulatory mechanisms of HSAF production involving specific transcription factors and the bacterial second messenger c‐di‐GMP.

miR-145-5p targets paxillin to attenuate angiotensin II-induced pathological cardiac hypertrophy via downregulation of Rac 1, pJNK, p-c-Jun, NFATc3, ANP and by Sirt-1 upregulation - Kuan-Ho Lin; V. Bharath Kumar; Tamilselvi Shanmugam; Marthandam Asokan Shibu; Ray-Jade Chen; Chia-Hua Kuo; Tsung-Jung Ho; V. Vijaya Padma; Yu-Lan Yeh; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Assessment of climate change effects on alpine summit vegetation in the transition of tropical to subtropical humid climate - Chu-Chia Kuo; Yu Su; Ho-Yih Liu; Cheng-Tao Lin (Plant Ecology, 2021)

Dynamic analysis of residential and enterprise water supply and leakage efficiencies - Ying Li; Yung-ho Chiu; Yushan Li; Hongyi Cen; Tai-Yu Lin (Environmental Science and Pollution Research, 2021)

Exploring the environmental and economic potential for biogas production from swine manure wastewater by life cycle assessment - Meng-Fen Shih; Chyi-How Lay; Chiu-Yue Lin; Shen-Ho Chang (Clean Technologies and Environmental Policy, 2021)

Influence of different fluidization and gasification parameters on syngas composition and heavy metal retention in a two-stage fluidized bed gasification process - Jia-Hong Kuo; Chiou-Liang Lin; Chang-Yu Ho; Jia-Chi Hung (Environmental Science and Pollution Research, 2021)

EndoPil: A Magnetically Actuated Swallowable Capsule for Weight Management: Development and Trials - Phuoc Thien Phan; Anthony Meng Huat Tiong; Muneaki Miyasaka; Lin Cao; Hung Leng Kaan; Khek Yu Ho; Soo Jay Phee (Annals of Biomedical Engineering, 2021)

Efficiency assessment of coal energy and non-coal energy under bound dynamic DDF DEA - Ying Li; Tai-Yu Lin; Yung-ho Chiu; Hongyi Cen; Yi-Nuo Lin (Environmental Science and Pollution Research, 2021)

In vitro study on α-amylase and α-glucosidase inhibitory activities of a new stigmastane-type steroid saponin from the leaves of Vernonia amygdalina - Hoang Le Tuan Anh; Le Ba Vinh; Le Thi Lien; Pham Viet Cuong; Masayoshi Arai; Tran Phuong Ha; Hoang Ngoc Lin; Ton That Huu Dat; Le Canh Viet Cuong; Young Ho Kim (Natural Product Research, 2021)

Biopharmaceutics Applications of Physiologically Based Pharmacokinetic Absorption Modeling and Simulation in Regulatory Submissions to the U.S. Food and Drug Administration for New Drugs - Fang Wu; Heta Shah; Min Li; Peng Duan; Ping Zhao; Sandra Suarez; Kimberly Raines; Yang Zhao; Meng Wang; Ho-pi Lin; John Duan; Lawrence Yu; et al. (The AAPS Journal, 2021)

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

Changes in arthropod community but not plant quality benefit a specialist herbivore on plants under reduced water availability - Po-An Lin; Chia-Ming Liu; Jia-Ang Ou; Cheng-Han Sun; Wen-Po Chuang; Chuan-Kai Ho; Natsuko Kinoshita; Gary W. Felton (Oecologia, 2021)

Dapagliflozin suppresses ER stress and protects doxorubicin-induced cardiotoxicity in breast cancer patients - Wei-Ting Chang; Yu-Wen Lin; Chung-Han Ho; Zhih-Cherng Chen; Ping-Yen Liu; Jhih-Yuan Shih (Archives of Toxicology, 2021)

Sea Urchins Play an Increasingly Important Role for Coral Resilience Across Reefs in Taiwan - Viet D. H. Dang; Pak-Yin Cheung; Chia-Ling Fong; Aziz J. Mulla; Jia-Ho Shiu; Che-Hung Lin; Yoko Nozawa (Frontiers in Marine Science, 2020)
Herbivores are an important functional group that control algae, create new space, and promote recruitment for coral recovery. However, on many coral reefs, overfishing has greatly decreased the density of herbivores, especially fishes and gastropods, impairing coral resilience. On such overfished reefs, remnant herbivores that are not target species of local fisheries, e.g., sea urchins, are expected to play an increasingly important role, yet few studies, except for those in the Caribbean and Kenya have examined non-fish herbivores in relation to coral resilience. Here, we conducted field surveys at 30 sites along three coral reefs in Taiwan between 2016 and 2017, to examine the relative importance of six key factors for coral resilience: herbivore abundance (fishes, gastropods, sea urchins), coral cover, macroalgal cover, habitat complexity, water depth, and wave exposure. The density of juvenile coral was used as a proxy of coral resilience. Diadematid sea urchins ( Echinothrix spp. and Diadema spp.) dominated most sites (19 of 30 sites) and multivariable regression models showed sea urchin density as the best positive predictor of coral juvenile density. The results elucidated the increasing role diadematid sea urchins play as remnant herbivores on overfished coral reefs in Taiwan. Given that overfishing is a widespread issue, this phenomenon may be occurring globally. More studies are needed to examine the role of remnant, but often ignored, sea urchin herbivory on coral resilience. Reef managers should consider monitoring locally remnant herbivores and incorporating them into management strategies.

Assessment of Applications of Design of Experiments in Pharmaceutical Development for Oral Solid Dosage Forms - Ge Bai; Zhijin Chen; Kimberly Raines; Hansong Chen; Kaushalkumar Dave; Ho-Pi Lin; Banu S. Zolnik (Journal of Pharmaceutical Innovation, 2020)

Osmotic stress induces gut microbiota community shift in fish - Keng Po Lai; Xiao Lin; Nathan Tam; Jeff Cheuk Hin Ho; Marty Kwok‐Shing Wong; Jie Gu; Ting Fung Chan; William Ka Fai Tse (Environmental Microbiology, 2020)
Summary Alteration of the gut microbiota plays an important role in animal health and metabolic diseases. However, little is known with respect to the influence of environmental osmolality on the gut microbial community. The aim of the current study was to determine whether the reduction in salinity affects the gut microbiota and identify its potential role in salinity acclimation. Using Oryzias melastigma as a model organism to perform progressive hypotonic transfer experiments, we evaluated three conditions: seawater control (SW), SW to 50% sea water transfer (SFW) and SW to SFW to freshwater transfer (FW). Our results showed that the SFW and FW transfer groups contained higher operational taxonomic unit microbiota diversities. The dominant bacteria in all conditions constituted the phylum Proteobacteria , with the majority in the SW and SFW transfer gut comprising Vibrio at the genus level, whereas this population was replaced by Pseudomonas in the FW transfer gut. Furthermore, our data revealed that the FW transfer gut microbiota exhibited a reduced renin–angiotensin system, which is important in SW acclimation. In addition, induced detoxification and immune mechanisms were found in the FW transfer gut microbiota. The shift of the bacteria community in different osmolality environments indicated possible roles of bacteria in facilitating host acclimation.

The effects of weather on daily emergency ambulance service demand in Taipei: a comparison with Hong Kong - Ho Ting Wong; Jen-Jia Lin (Theoretical and Applied Climatology, 2020)

Relationship Between Seismic Moment and Source Duration for Seismogenic Earthquakes in Taiwan: Implications for the Product of Static Stress Drop and the Cube of Rupture Velocity - Ruey-Der Hwang; Cheng-Ying Ho; Tzu-Wei Lin; Wen-Yen Chang; Yi-Ling Huang; Cai-Yi Lin; Chiung-Yao Lin (Pure and Applied Geophysics, 2020)

Household airborne endotoxin associated with asthma and allergy in elementary school-age children: a case–control study in Kaohsiung, Taiwan - Yu-Chuan Yen; Chun-Yuh Yang; Tsu-Nai Wang; Pei-Chun Yen; Chi-Kung Ho; Kristina D. Mena; Tzu-Chi Lee; Kang-Shin Chen; Yuan-Chung Lin; Pei-Shih Chen (Environmental Science and Pollution Research, 2020)
To evaluate the association between the presence of asthma and allergy, and airborne endotoxin in homes of school-age children in Kaohsiung City, Taiwan, with a case–control study design by matching the age and class exposure. Data collection of home visits included an interviewer-administered questionnaire and air sampling of participants’ homes for endotoxin, bacteria, and fungi, as well as temperature and relative humidity measurements. Endotoxin was detected in all air samples with a median value of 0.67 EU m −3 . In the adjusted logistic regression model, household airborne endotoxin was associated with higher prevalence of asthma and allergy; OR = 4.88 (95% CI 1.16–20.55) for Q3 (between 0.67 and 1.97 EU m −3 ) vs. Q1 (< 0.31 EU m −3 ), with statistical significance. Airborne fungi were associated with higher prevalence of asthma and allergy; OR = 4.47 (95% CI 1.13–17.69) for Q3 (between 314 and 699 CFU m −3 ) vs. Q1 (< 159 CFU m −3 ) in adjusted logistic regression models. Airborne endotoxin and fungi were significantly associated with children’s asthma and allergy.

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

Integrating Patient-Specific Electrocardiogram Signals and Image-Based Computational Fluid Dynamics Method to Analyze Coronary Blood Flow in Patients during Cardiac Arrhythmias - Szu-Hsien Chou; Kuan-Yu Lin; Zhen-Ye Chen; Chun-Jung Juan; Chien-Yi Ho; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to use the computational fluid dynamics (CFD) method, patient-specific electrocardiogram (ECG) signals, and computed tomography three-dimensional image reconstruction technique to investigate the blood flow in coronary arteries during cardiac arrhythmia. Methods Two patients with premature ventricular contraction-type cardiac arrhythmia and one with atrial fibrillation-type cardiac arrhythmia were investigated. The inlet velocity of the coronary artery in simulation was applied with the measured velocity profile of the left ventricular outflow tract (LVOT) from the Doppler echocardiography. The measured patient central aortic blood pressure waveform was employed for the coronary artery outlet in simulation. The no-slip boundary condition was applied to the arterial wall. Results For the patient with irregular cardiac rhythms (Case I), the coronary blood flow rate under the shortened and lengthened cardiac rhythms were 0.66 and 0.96 mL/s, respectively. In Case II, the maximum velocity at the LVOT under a normal heartbeat was found to be 101 cm/s, whereas the average value was 73 cm/s. In Case III, the patient was also diagnosed with a congenital stenosis problem at the myocardial bridge (MCB) at the LAD. The measured blood flow rate at the MCB of the LAD for the three heartbeats in Case III was found to be 0.68, 1.08, and 1.14 mL/s. Conclusion The integration of patient-specific ECG signals and image-based CFD methods can clearly analyze hemodynamic information for patients during cardiac arrhythmia. The cardiac arrhythmia can reduce the blood flow in the coronary arteries.

A stochastic multi-objective optimization decision model for energy facility allocation: a case of liquefied petroleum gas station - Ming-Der Yang; Yi-Ping Chen; Chien-Tsung Wang; Ming-Jay Deng; Yu-Hao Lin; Ho-Wen Chen (Clean Technologies and Environmental Policy, 2020)

Resource availability affects temporal variation of phytoplankton size structure in the Kuroshio east of Taiwan - Fan‐Sian Lin; Pei‐Chi Ho; Akash R. Sastri; Chung‐Chi Chen; Gwo‐Ching Gong; Sen Jan; Chih‐hao Hsieh (Limnology and Oceanography, 2020)
The on‐going discussion concerning how environmental factors determine phytoplankton size structure has centered around two hypotheses: (H1) The resource‐size relationship predicts that normalized biovolume size spectrum (NBSS) slopes for phytoplankton are progressively shallower with increasing resource availability and (H2) The temperature‐size relationship predicts that phytoplankton NBSS slopes steepen with increasing water temperature. To test these hypotheses, we examined 72 phytoplankton assemblage collections in the Kuroshio east of Taiwan. Total phytoplankton biomass was used as a proxy for resource availability instead of nutrients because nutrients are depleted and do not represent resource availability for oligotrophic seas. We found no significant relationship between NBSS slopes with temperature, providing little support for the temperature‐size rule. In contrast, a positive relationship between NBSS slopes and total biomass for most of the year lends general support to the resource‐size relationship, except during the winter and early spring. To explain this exception, we hypothesize that resource pulses occurring during the cold seasons are used more efficiently by small cells and promote faster growth of small relative to large phytoplankton because these pulses take place after a long period of resource depletion in oligotrophic seas; thus, the NBSS slopes become much steeper than would be expected from a positive resource‐size relationship. This deviation can be considered as nonsteady state in terms of phytoplankton size structure relative to resources. Nevertheless, we cannot rule out the possibility that grazing effects also play an important role in controlling phytoplankton size structure.

Anti-inflammatory Effect of AZD6244 on Acrolein-Induced Neuroinflammation - Wen-Chien Ho; Chia-Chi Hsu; Hui-Ju Huang; Hsiang-Tsui Wang; Anya Maan-Yuh Lin (Molecular Neurobiology, 2020)

Secondary metabolites from the fermented rice of the fungus Monascus purpureus and their bioactivities - Ho-Cheng Wu; Ming-Jen Cheng; Ming-Der Wu; Jih-Jung Chen; Yen-Lin Chen; Hsun-Shuo Chang; Kai-Ping Chen (Natural Product Research, 2019)

Marine 3D seismic volumes from 2D seismic survey with large streamer feathering - Liang-Fu Lin; Ho-Han Hsu; Char-Shine Liu; Kuo-Han Chao; Chia-Chun Ko; Shye-Dong Chiu; Hsin-Sung Hsieh; Yu-Fang Ma; Song-Chuen Chen (Marine Geophysical Research, 2019)

Transcriptome analysis of rice-seedling roots under soil–salt stress using RNA-Seq method - Anil Kumar Nalini Chandran; Jeong-Won Kim; Yo-Han Yoo; Hye Lin Park; Yeon-Ju Kim; Man-Ho Cho; Ki-Hong Jung (Plant Biotechnology Reports, 2019)

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

The neural correlates of perceived energy levels in older adults with late-life depression - Charlene L. M. Lam; Ho-Ling Liu; Chih-Mao Huang; Yau-Yau Wai; Shwu-Hua Lee; Jenny Yiend; Chemin Lin; Tatia M. C. Lee (Brain Imaging and Behavior, 2019)

Crops For the Future (CFF): an overview of research efforts in the adoption of underutilised species - Peter J. Gregory; Sean Mayes; Chai Hui Hui; Ebrahim Jahanshiri; Advina Julkifle; Giva Kuppusamy; Ho Wai Kuan; Tan Xin Lin; Festo Massawe; T. A. S. T. M. Suhairi; Sayed N. Azam-Ali (Planta, 2019)

Research on the effect of coal seam inclination on gas migration channels at fully mechanized coal mining face - Pengxiang Zhao; Risheng Zhuo; Shugang Li; Chun-Hsing Ho; Haifei Lin; Hui Liu (Arabian Journal of Geosciences, 2019)

Design and functions of floating architecture – a review - Yuan-Ho Lin; Yung Chih Lin; Han-Shih Tan (Marine Georesources & Geotechnology, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Using a numerical method to precisely evaluate the alpha angle in a hip image - Chung-Liang Lai; Wei-Min Chi; Ying-Jui Ho; Chien-Chung Lin; Hsiao-Che Lin; Chin-Liang Kuo; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2019)

Slope deformation monitoring in the Jiufenershan landslide using time domain reflectometry technology - Shei-Chen Ho; I-Hui Chen; Yu-Shu Lin; Jun-Yang Chen; Miau-Bin Su (Landslides, 2019)

Designing a Novel Drug Delivering Nerve Guide: A Preliminary Study - Scott Ho; Pratima Labroo; Keng-Min Lin; Himanshu Sant; Jill Shea; Bruce Gale; Jay Agarwal (Journal of Medical and Biological Engineering, 2019)

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

Dissolution and Translational Modeling Strategies Toward Establishing an In Vitro-In Vivo Link—a Workshop Summary Report - Tycho Heimbach; Sandra Suarez-Sharp; Maziar Kakhi; Nico Holmstock; Andrés Olivares-Morales; Xavier Pepin; Erik Sjögren; Eleftheria Tsakalozou; Paul Seo; Min Li; Xinyuan Zhang; Ho-Pi Lin; et al. (The AAPS Journal, 2019)

Evaluation of landslides process and potential in Shenmu sub-watersheds, central Taiwan - Bor-Shiun Lin; Kent Thomas; Chun-Kai Chen; Hsing-Chuan Ho (Landslides, 2019)

A new association between goblet worms (Entoprocta) and xeniid corals (Cnidaria) - Vianney Denis; Yu Ting Vicky Lin; Ming Jay Ho (Marine Biodiversity, 2019)

Responses of legumes and grasses to non-, moderate, and dense shade in Missouri, USA. I. Forage yield and its species-level plasticity - Kejia Pang; J. W. Van Sambeek; Nadia E. Navarrete-Tindall; Chung-Ho Lin; Shibu Jose; H. E. Garrett (Agroforestry Systems, 2019)

Responses of legumes and grasses to non-, moderate, and dense shade in Missouri, USA. II. Forage quality and its species-level plasticity - Kejia Pang; J. W. Van Sambeek; Nadia E. Navarrete-Tindall; Chung-Ho Lin; Shibu Jose; H. E. Garrett (Agroforestry Systems, 2019)

Seismic imaging of the Formosa Ridge cold seep site offshore of southwestern Taiwan - Ho-Han Hsu; Char-Shine Liu; Sumito Morita; Shu-Lin Tu; Saulwood Lin; Hideaki Machiyama; Wataru Azuma; Chia-Yen Ku; Song-Chuen Chen (Marine Geophysical Research, 2018)

A new C -glycosyl flavone and a new neolignan glycoside from Passiflora edulis Sims peel - Yue Hu; Lin Jiao; Min-Hong Jiang; Sheng Yin; Pan Dong; Zhi-Min Zhao; De-Po Yang; Pei-Tsai Ho; Dong-Mei Wang (Natural Product Research, 2018)

Heroin Use Could Be Also Associated with Ruptured Aortic Aneurysms - Tung-Ho Wu; Hsing-Lin Lin (Translational Stroke Research, 2018)

Endocrine-Disrupting Activities and Organic Contaminants Associated with Oil and Gas Operations in Wyoming Groundwater - Christopher D. Kassotis; Danh C. Vu; Phuc H. Vo; Chung-Ho Lin; Jennifer N. Cornelius-Green; Sharyle Patton; Susan C. Nagel (Archives of Environmental Contamination and Toxicology, 2018)

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Brain structural concomitants of resting state heart rate variability in the young and old: evidence from two independent samples - Hyun Joo Yoo; Julian F. Thayer; Steven Greening; Tae-Ho Lee; Allison Ponzio; Jungwon Min; Michiko Sakaki; Lin Nga; Mara Mather; Julian Koenig (Brain Structure and Function, 2018)

The impact on food security and future adaptation under climate variation: a case study of Taiwan’s agriculture and fisheries - Ching-Hsien Ho; Huu-Sheng Lur; Ming-Hwi Yao; Fang-Ching Liao; Ying-Ting Lin; Nobuyuki Yagi; Hsueh-Jung Lu (Mitigation and Adaptation Strategies for Global Change, 2018)

Dose Verification for Tumor Motion with Different Treatment Planning Systems: A Dynamic Thorax Phantom Study - Shih-Neng Yang; Chun-Wei Lin; Mu-Bai Chang; Geoffrey G. Zhang; Kuei-Ting Chou; Yu-Rou Chiou; Shung-Shung Sun; Louis Lui; Tsung-Jung Ho; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Using nonlinear finite element models to analyse stress distribution during subluxation and torque required for dislocation of newly developed total hip structure after prosthetic impingement - Wei-Min Chi; Chien-Chung Lin; Ying-Jui Ho; Hsiao-Che Lin; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2018)

Far infrared promotes wound healing through activation of Notch1 signaling - Yung-Ho Hsu; Yuan-Feng Lin; Cheng-Hsien Chen; Yu-Jhe Chiu; Hui-Wen Chiu (Journal of Molecular Medicine, 2017)

17β-Estradiol and/or estrogen receptor alpha blocks isoproterenol-induced calcium accumulation and hypertrophy via GSK3β/PP2A/NFAT3/ANP pathway - Peiying Pai; Bharath Kumar Velmurugan; Chia-Hua Kuo; Chung-Yi Yen; Tsung-Jung Ho; Yueh-Min Lin; Yu-Feng Chen; Chao-Hung Lai; Cecilia Hsuan Day; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2017)

Groundwater origins and recharge in a well field near Chien-Shih, Shinchu, Taiwan - Pei-Ying Lin; Louis Loung-Yie Tsai; Chung-Ho Wang; Kuei-Wen Chang; Yu-Yen Sheng; I-Tzu Chu; Wang-Ru Lee (Sustainable Water Resources Management, 2017)

Development of a TaqMan probe-based insulated isothermal PCR (TiiPCR) for the detection of Acidovorax citrulli, the bacterial pathogen of watermelon fruit blotch - Pei-Yi Wu; Lien-Chun Ho; Jun-Jie Chang; Kuo-Ching Tzeng; Wen-Ling Deng; Yi-Hsien Lin (European Journal of Plant Pathology, 2017)

Novel non-contact control system of electric bed for medical healthcare - Chi-Chun Lo; Shang-Ho Tsai; Bor-Shyh Lin (Medical & Biological Engineering & Computing, 2017)

Distribution of a Coastal Delphinid Under the Impact of Long-Term Habitat Loss: Indo-Pacific Humpback Dolphins off Taiwan’s West Coast - Leszek Karczmarski; Shiang-Lin Huang; Wai-Ho Wong; Wei-Lun Chang; Stephen C.Y. Chan; Mark Keith (Estuaries and Coasts, 2017)

Effects of Porphyromonas gingivalis on Titanium Surface by Different Clinical Treatment - Nominzul Batsukh; Sheng Wei Feng; Wei Fang Lee; Sy-Jye Leu; Pei-Yo Tsai; Kuo-Ning Ho; Che Tong Lin; Ching-Hua Su; Wei-Jen Chang (Journal of Medical and Biological Engineering, 2017)

Rapid Fabrication of a Cell-Seeded Collagen Gel-Based Tubular Construct that Withstands Arterial Pressure - Ho-Yi Tuan-Mu; Po-Ching Lu; Pei-Yuan Lee; Chien-Chih Lin; Chun-Jung Chen; Lynn L.H. Huang; Jia-Horng Lin; Jin-Jia Hu (Annals of Biomedical Engineering, 2016)

Effects of probiotics on soil microbial activity, biomass and enzymatic activity under cover crops in field and greenhouse studies - Ahsan M. Rajper; Ranjith P. Udawatta; Robert J. Kremer; Chung-ho Lin; Shibu Jose (Agroforestry Systems, 2016)

Clinacanthus nutans Extracts Modulate Epigenetic Link to Cytosolic Phospholipase A2 Expression in SH-SY5Y Cells and Primary Cortical Neurons - Charlene Siew-Hon Tan; Christabel Fung-Yih Ho; Swan-Ser Heng; Jui-Sheng Wu; Benny Kwong-Huat Tan; Yee-Kong Ng; Grace Y. Sun; Teng-Nan Lin; Wei-Yi Ong (NeuroMolecular Medicine, 2016)

Review on Saussurea laniceps, a potent medicinal plant known as “snow lotus”: botany, phytochemistry and bioactivities - Qi-Lei Chen; Xi-Yu Chen; Lin Zhu; Hu-Biao Chen; Hing-Man Ho; Wing-Ping Yeung; Zhong-Zhen Zhao; Tao Yi (Phytochemistry Reviews, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Evaluation of soil erosion risk for watershed management in Shenmu watershed, central Taiwan using USLE model parameters - B. S. Lin; K. Thomas; C. K. Chen; H. C. Ho (Paddy and Water Environment, 2016)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Theoretical Analysis of Total Hip Dislocation and Comparison of Hemispherical Cup and Newly Developed Cup - Hsiao-Che Lin; Wei-Min Chi; Ying-Jui Ho; Chien-Chung Lin; Jian-Horng Chen (Journal of Medical and Biological Engineering, 2015)

Molecular phylogeny and the underestimated species diversity of the endemic white‐bellied rat (Rodentia: Muridae: Niviventer ) in Southeast Asia and China - Liang Lu; Deyan Ge; Douglas Chesters; Simon Y. W. Ho; Ying Ma; Guichang Li; Zhixin Wen; Yongjie Wu; Jun Wang; Lin Xia; Jingli Liu; Tianyu Guo; et al. (Zoologica Scripta, 2015)
The white‐bellied rat, Niviventer , is a genus endemic to Southeast Asia and China. However, the interspecific phylogenetic relationships and species diversity of this genus remain poorly understood. In the present study, single and multi‐locus analyses were performed. Phylogenetic reconstruction on Cytochrome b (512 individuals, including data from Genbank) revealed five major clades with approximately 35 operational taxonomic units ( OTU s), a number twice the existing taxonomy. The first clade ( N . langbianis species group) was the earliest diverged. The second clade ( N. fulvescens species group) diverged in Southeast Asia, the south and lower altitude regions of the Hengduan Mountains, and Southeast China. The third clade (the N. eha species group) is endemic to high altitudes in Northwest Yunnan and the central region of Himalaya. The fourth clade (the N. andersoni species group), is mainly confined to alpine regions of the Hengduan Mountains. The fifth clade ( N . confucianus species group) is mainly distributed in the north and higher altitude regions of eastern Himalaya, the Hengduan Mountains and Taiwan, with the complex also invading central and northern China. Results from the combined dataset of four genes (Cytochrome b, Cytochrome oxidase subunit I, the D‐loop sequence of the mitochondrial genome and the first exon of the nuclear interphotoreceptor retinoid binding protein) for 82 representative individuals from China generally coincide with the result of the single gene, with 12 OTU s identified. These results provide a preliminary framework for the existing classification of this highly diversified genus. The divergence time of Niviventer based on the four gene topology was dated to the late Miocene ~6.41 Ma. Significant differences were detected in the general body form changes among these units based on voucher specimens. Moreover, geometric morphometric analysis of the cranium shape of voucher specimens indicated significant differences among five major species groups. Shape divergence of the cranium among several OTU s within the N. confucinaus complex is also significant. Our results provide further evidence for rapid and highly underestimated diversification of Niviventer both in genetics and morphology.

Metabolites of Scutellariae Radix Inhibit Injury of Endothelial Cells in Hypoxia Device - Chia-Lun Chao; Shiuan-Pey Lin; Yu-Chi Hou; Pei-Dawn Lee Chao; Nen-Chung Chang; Yu-Ching Huang; Feng-Ming Ho (Journal of Medical and Biological Engineering, 2015)

Novel Link of Anti-apoptotic ATF3 with Pro-apoptotic CTMP in the Ischemic Brain - Chien-Yu Huang; Jin-Jer Chen; Jui-Sheng Wu; Hsin-Da Tsai; Heng Lin; Yu-Ting Yan; Chung Y. Hsu; Yuan-Soon Ho; Teng-Nan Lin (Molecular Neurobiology, 2015)

Characterization of alcohol dehydrogenase from Kangiella koreensis and its application to production of all-trans-retinol - Seung-Hye Hong; Ho-Phuong-Thuy Ngo; Lin-Woo Kang; Deok-Kun Oh (Biotechnology Letters, 2015)

Methodology of disaster risk assessment for debris flows in a river basin - Ing-Jia Chiou; Ching-Ho Chen; Wei-Lin Liu; Shiao-Mei Huang; Yu-Min Chang (Stochastic Environmental Research and Risk Assessment, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Engineering leaf carbon metabolism to improve plant productivity - Man-Ho Cho; Hye Lin Park; Tae-Ryong Hahn (Plant Biotechnology Reports, 2015)

Genetic diversity and identification of race 3 of Fusarium oxysporum f. sp. lactucae in Taiwan - Ying-Hong Lin; Po-Jung Lai; Tao-Ho Chang; Yu-Ling Wan; Jenn-Wen Huang; Jin-Hsing Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2014)

Development and characterization of nine polymorphic microsatellite markers from the sword prawn Parapenaeopsis hardwickii using PCR-based isolation of microsatellite arrays (PIMA) - Chuan-Wen Ho; Tzong-Der Tzeng; Tzen-Yuh Chiang; Chih-Yao Li; Feng-Jiau Lin (Conservation Genetics Resources, 2014)

Nanomedicine for glaucoma: sustained release latanoprost offers a new therapeutic option with substantial benefits over eyedrops - Tina T. Wong; Gary D. Novack; Jayaganesh V. Natarajan; Ching Lin Ho; Hla M. Htoon; Subbu S. Venkatraman (Drug Delivery and Translational Research, 2014)

The role of serine 190 in FOXO nuclear export and cell death induction in Drosophila melanogaster - Yoon Ki Hong; Dahye Lee; Soojin Hwang; Se Min Bang; Haemin Jeong; Seoyun Choi; Tan-Viet Phamd; Lin-Woo Kang; Young-Ha Lee; Kyoung Sang Cho; Guang-Ho Cha (Genes & Genomics, 2014)

Commonly Used Excipients Modulate UDP-Glucuronosyltransferase 2B7 Activity to Improve Nalbuphine Oral Bioavailability in Humans - Hong-Jaan Wang; Cheng-Huei Hsiong; Shung-Tai Ho; Min-Jen Lin; Tung-Yuan Shih; Pei-Wei Huang; Oliver Yoa-Pu Hu (Pharmaceutical Research, 2014)

Non-alcoholic fatty liver disease and risk of in-stent restenosis after bare metal stenting in native coronary arteries - Ke-Qing Shi; Fa-Ling Wu; Wen-Yue Liu; Chen-Chen Zhao; Chang-Xi Chen; Yao-Yao Xie; Sheng-Jie Wu; Xian-Feng Lin; Yong-Ping Chen; Danny Ka-Ho Wong; Man-Fung Yuen; Ming-Hua Zheng (Molecular Biology Reports, 2014)

Spatial-temporal scales of Green Island wake due to passing of the Kuroshio current - Shih-Jen Huang; Chung-Ru Ho; Sheng-Lin Lin; Shin-Jye Liang (International Journal of Remote Sensing, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

Increased risk of colorectal malignant neoplasm in patients with nonalcoholic fatty liver disease: a large study - Xian-Feng Lin; Ke-Qing Shi; Jie You; Wen-Yue Liu; Ying-Wan Luo; Fa-Ling Wu; Yong-Ping Chen; Danny Ka-Ho Wong; Man-Fung Yuen; Ming-Hua Zheng (Molecular Biology Reports, 2014)

Anti-apoptotic protein BRE/BRCC45 attenuates apoptosis through maintaining the expression of caspase inhibitor XIAP in mouse Lewis lung carcinoma D122 cells - Yiu-Loon Chui; Chun-Hung Ma; Wei Li; Zhenyu Xu; Yao Yao; Frances Ka-Yin Lin; John Yeuk-Hon Chan; Kenneth Ka-Ho Lee (Apoptosis, 2014)

pIMP-PH114 Carrying bla IMP-4 in a Klebsiella pneumoniae Strain is Closely Related to Other Multidrug-Resistant IncA/C2 Plasmids - Pak-Leung Ho; Wai-U Lo; Jane Chan; Yuk-Yam Cheung; Kin-Hung Chow; Wing-Cheong Yam; Chi-Ho Lin; Tak-Lun Que (Current Microbiology, 2014)

Expression characterization and promoter activity analysis of the tilapia (Oreochromis niloticus) myosin light chain 3 promoter in skeletal muscle of fish - Yu-Ho Lin; Kuan-Chieh Peng; Chieh-Yu Pan; Zhi-Hong Wen; Jyh-Yih Chen (Transgenic Research, 2014)

Global Hunger: A Challenge to Agricultural, Food, and Nutritional Sciences - Shiuan-Huei Wu; Chi-Tang Ho; Sui-Lin Nah; Chi-Fai Chau (Critical Reviews in Food Science and Nutrition, 2014)

Investigating the adaptation of muscle oxygenation to resistance training for elders and young men using near-infrared spectroscopy - Tai-You Lin; Linda L. Lin; Ting-Chuan Ho; Jia-Jin J. Chen (European Journal of Applied Physiology, 2014)

Evaluating the protective efficacy of antigen combinations against P hotobacterium damselae ssp. piscicida infections in cobia, Rachycentron canadum L. - L‐P Ho; C‐J Chang; H‐C Liu; H‐L Yang; J H‐Y Lin (Journal of Fish Diseases, 2014)
Cobia, Rachycentron canadum L., is a very important aquatic fish that faces the risk of infection with the bacterial pathogen P hotobacterium damselae ssp. piscicida , and there are few protective approaches available that use multiple antigens. In the present study, potent bivalent antigens from P . damselae ssp. piscicida showed more efficient protection than did single antigens used in isolation. In preparations of three antigens that included recombinant heat shock protein 60 ( rHSP 60), recombinant α‐enolase ( rENOLASE ) and recombinant glyceraldehyde‐3‐phosphate dehydrogenase ( rGAPDH ), we analysed the doses that elicited the best immune responses and found that this occurred at a total of 30 μg of antigen per fish. Subsequently, vaccination of fish with rHSP 60, rENOLASE and rGAPDH achieved 46.9, 52 and 25% relative per cent survival (RPS), respectively. In addition, bivalent subunit vaccines – combination I ( rHSP 60 + rENOLASE ), combination II ( rENOLASE + rGAPDH ) and combination III ( rHSP 60 + rGAPDH ) – were administered and the RPS in these groups (65.6, 64.0 and 48.4%, respectively), was higher than that achieved with single‐antigen administration. Finally, in combination IV , the trivalent vaccine rHSP 60 + rENOLASE + rGAPDH , the RPS was 1.6%. Taken together, our results suggest that combinations of two antigens may achieve a better efficiency than monovalent or trivalent antigens, and this may provide new insights into pathogen prevention strategies.

Responses to booster hepatitis B vaccination are significantly correlated with genotypes of human leukocyte antigen (HLA)-DPB1 in neonatally vaccinated adolescents - Tzu-Wei Wu; Chen-Chung Chu; Tzu-Ying Ho; Huei-Wen Chang Liao; Sheng-Kai Lin; Marie Lin; Hans Hsienhong Lin; Li-Yu Wang (Human Genetics, 2013)

Molecular Characterization of an Atypical IncX3 Plasmid pKPC-NY79 Carrying bla KPC-2 in a Klebsiella pneumoniae - Pak-Leung Ho; Yuk-Yam Cheung; Wai-U Lo; Zhen Li; Kin-Hung Chow; Chi-Ho Lin; Jasper Fuk-Woo Chan; Vincent Chi-Chung Cheng (Current Microbiology, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

Geochemistry of ultramafic xenoliths in Cenozoic alkali basalts from Jiangsu province, eastern China and their geological implication - SHAO-WEI HUANG; YUNG-TAN LEE; JU-CHIN CHEN; KUNG-SUAN HO; MENG-LUNG LIN; YEN-TSUI HU; REN-YI HUANG (Journal of Earth System Science, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Effects of design parameters of total hip components on the impingement angle and determination of the preferred liner skirt shape with an adequate oscillation angle - Hsiao-Che Lin; Wei-Min Chi; Ying-Jui Ho; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2013)

Iodine content in commonly consumed food in Hong Kong and its changes due to cooking - Stephen Chung; Andy Chan; Ying Xiao; Violette Lin; Y.Y. Ho (Food Additives & Contaminants Part B-Surveillance, 2013)

Erratum to: Magnetic Nanoparticle Targeted Hyperthermia of Cutaneous Staphylococcus aureus Infection - Min-Ho Kim; Itsukyo Yamayoshi; Steven Mathew; Hubert Lin; Joseph Nayfach; Scott I. Simon (Annals of Biomedical Engineering, 2013)

Magnetic Nanoparticle Targeted Hyperthermia of Cutaneous Staphylococcus aureus Infection - Min-Ho Kim; Itsukyo Yamayoshi; Steven Mathew; Hubert Lin; Joseph Nayfach; Scott I. Simon (Annals of Biomedical Engineering, 2013)

Allelopathic Exudates of Cogongrass (Imperata cylindrica): Implications for the Performance of Native Pine Savanna Plant Species in the Southeastern US - Donald L. Hagan; Shibu Jose; Chung-Ho Lin (Journal of Chemical Ecology, 2013)

Lipopolysaccharide/adenosine triphosphate-mediated signal transduction in the regulation of NLRP3 protein expression and caspase-1-mediated interleukin-1β secretion - Pei-Chun Liao; Louis Kuoping Chao; Ju-Ching Chou; Wei-Chih Dong; Chien-Nan Lin; Chai-Yi Lin; Ann Chen; Shuk-Man Ka; Chen-Lung Ho; Kuo-Feng Hua (Inflammation Research, 2013)

Folic acid inhibits endothelial cell proliferation through activating the cSrc/ERK 2/NF-κB/p53 pathway mediated by folic acid receptor - Shyr-Yi Lin; Woan-Ruoh Lee; Yi-Fan Su; Sung-Po Hsu; Hsu-Chen Lin; Pei-Yin Ho; Tien-Chi Hou; Yu-Pei Chou; Chun-Ting Kuo; Wen-Sen Lee (Angiogenesis, 2012)

High glucose increases nitric oxide generation in lipopolysaccharide-activated macrophages by enhancing activity of protein kinase C-α/δ and NF-κB - Kuo-Feng Hua; Szu-Hsuan Wang; Wei-Chih Dong; Chai-Yi Lin; Chen-Lung Ho; Tzu-Hua Wu (Inflammation Research, 2012)

Development of transgenic watermelon resistant to Cucumber mosaic virus and Watermelon mosaic virus by using a single chimeric transgene construct - Ching-Yi Lin; Hsin-Mei Ku; Yi-Hua Chiang; Hsiu-Yin Ho; Tsong-Ann Yu; Fuh-Jyh Jan (Transgenic Research, 2012)

Photocatalytic Degradation of Reactive Black 5 by Fish Scale-Loaded TiO2 Composites - Li-Ngee Ho; Soon-An Ong; Yee Lin See (Water, Air, & Soil Pollution, 2012)

Fasudil, a Rho-kinase inhibitor, protects against excessive endurance exercise training-induced cardiac hypertrophy, apoptosis and fibrosis in rats - Tsung-Jung Ho; Chi-Chang Huang; Chih-Yang Huang; Wan-Teng Lin (European Journal of Applied Physiology, 2012)

Pollution and variation of stream nitrate in a protected high-mountain watershed of Central Taiwan: evidence from nitrate concentration and nitrogen and oxygen isotope compositions - Tsung-Ren Peng; Hsing-Juh Lin; Chung-Ho Wang; Tsang-Sen Liu; Shuh-Ji Kao (Environmental Monitoring and Assessment, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Reemerging of enterovirus 71 in Taiwan: the age impact on disease severity - S.-M. Wang; T.-S. Ho; H.-C. Lin; H.-Y. Lei; J.-R. Wang; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Effect of C-terminal truncation on enzyme properties of recombinant amylopullulanase from Thermoanaerobacter pseudoethanolicus - Fu-Pang Lin; Yi-Hsuan Ho; Hsu-Yang Lin; Hui-Ju Lin (Extremophiles, 2012)

Increasing trend of primary NO2 exhaust emission fraction in Hong Kong - Linwei Tian; Sarah R. Hossain; Hualiang Lin; Kin Fai Ho; Shun Cheng Lee; Ignatius T. S. Yu (Environmental Geochemistry and Health, 2011)

Variability of sea surface temperature and warm pool area in the South China Sea and its relationship to the western Pacific warm pool - Chun-Yi Lin; Chung-Ru Ho; Quanan Zheng; Shih-Jen Huang; Nan-Jung Kuo (Journal of Oceanography, 2011)

Application of a Sustainable Fisheries Development Indicator System (SFDIS) for Better Management Outcomes in Taiwan Offshore and Coastal Fishery - Wen-Hong Liu; Kun-Lung Lin; Hao-Tang Jhan; Ta-Ly Lin; De-Lu Ding; Ching-Hsien Ho (Coastal Management, 2011)

QTL identification of flowering time at three different latitudes reveals homeologous genomic regions that control flowering in soybean - Weixian Liu; Moon Young Kim; Yang Jae Kang; Kyujung Van; Yeong-Ho Lee; Peerasak Srinives; Dong Lin Yuan; Suk-Ha Lee (Theoretical and Applied Genetics, 2011)

Implications of the Up-regulation of Genes Encoding Protein Degradation Enzymes and Heat Shock Protein 90 for Intertidal Green Macroalga Ulva fasciata Against Hypersalinity-Induced Protein Oxidation - Ming-Shiuan Sung; Yuan-Ting Hsu; Kuan-Lin Ho; Tse-Min Lee (Marine Biotechnology, 2011)

A Review of the Major Penaeid Shrimp EST Studies and the Construction of a Shrimp Transcriptome Database Based on the ESTs from Four Penaeid Shrimp - Jiann-Horng Leu; Shu-Hwa Chen; Yu-Bin Wang; Yen-Chen Chen; Sheng-Yao Su; Chung-Yen Lin; Jan-Ming Ho; Chu-Fang Lo (Marine Biotechnology, 2011)

Immobilization of silver in polypropylene membrane for anti-biofouling performance - Xiaoying Zhu; Lin Tang; Kin-Ho Wee; Yong-Hong Zhao; Renbi Bai (Biofouling, 2011)

Trace metal cycling in the deep water of the South China Sea: The composition, sources, and fluxes of sinking particles - Tung-Yuan Ho; Wen-Chen Chou; Hui-Ling Lin; David D. Sheu (Limnology and Oceanography, 2011)
Moored sediment traps were deployed for 1 yr at depths of 120, 600, and 3500 m in the water column to investigate the trace metal (M) (Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn) composition, sources, and fluxes of deep‐water sinking particles. Vertical transport for most of the metals at 120 m was strongly associated with organic matter production, and the major part of many of the metals in the sinking particles was of anthropogenic origin. Although the lithogenic fraction in deeper waters greatly increased with depth, significant proportions of the nonlithogenic and nonintracellular fractions were still observed when using M : Al or M : P ratios as indicators, particularly for Zn, Cu, Ni, Co, and Mn. Because particles from horizontal transport and sediment resuspension are known to be lithogenic in the deep basin, the trace metals in sinking particles in the twilight zone and deep water, which feature significantly elevated M : Al ratios, originate from the downward transport of anthropogenic or authigenic origins. With increasing inputs from anthropogenic aerosols over large oceanic regions globally, the coupling and transport of some trace metals originating from anthropogenic aerosols, such as Zn, Cu, Co, and Ni, with sinking organic particles has become an important pathway for trace metal cycling not only in the euphotic zone, but also in the twilight zone and deeper waters.

IL-29/IL-28A suppress HSV-1 infection of human NT2-N neurons - Lin Zhou; Jieliang Li; Xu Wang; Li Ye; Wei Hou; Jie Ho; He Li; Wenzhe Ho (Journal of NeuroVirology, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Celecoxib induces heme oxygenase-1 expression in macrophages and vascular smooth muscle cells via ROS-dependent signaling pathway - Jang-Shiun Wang; Feng-Ming Ho; Hao-Cheng Kang; Wan-Wan Lin; Kuo-Chin Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

Effects of Tai Chi on adiponectin and glucose homeostasis in individuals with cardiovascular risk factors - Rei-Yeuh Chang; Malcolm Koo; Meng-Ying Ho; Zi-Zi Lin; Zer-Ran Yu; Yen-Fen Lin; Be-Jen Wang (European Journal of Applied Physiology, 2011)

Dietary patterns and breast cancer risk among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Jian-Hua Fu; Shou-Zhen Cheng; Yu-Ming Chen; Fang-Yu Lin (Cancer Causes & Control, 2011)

Constitutive expression of a fungal glucose oxidase gene in transgenic tobacco confers chilling tolerance through the activation of antioxidative defence system - Subbiyan Maruthasalam; Yi Lun Liu; Ching Mei Sun; Pei Ying Chen; Chih Wen Yu; Pei Fang Lee; Chin Ho Lin (Plant Cell Reports, 2010)

Trace metal cycling in the surface water of the South China Sea: Vertical fluxes, composition, and sources - Tung-Yuan Ho; Wen-Chen Chou; Ching-Ling Wei; Fei-Jan Lin; George T. F. Wong; Hui-Ling Line (Limnology and Oceanography, 2010)
We deployed floating traps in the surface waters of the South China Sea on four occasions at depths of 30 m, 100 m, and 160 m from 2006 to 2007 to quantify vertical metal fluxes in the surface water and examine trace metal composition in the sinking particles to investigate their sources. The elements determined include 13 trace metals and 8 major elements. The fluxes for most of the bioactive elements at 30 m varied markedly during different seasons and strongly co‐varied with organic matter production, but the fluxes at 160 m were low and consistent under different seasons, showing that most of the elements were internally recycled in the surface water during productive seasons. Most of the bioactive trace metals in sinking particles were correlated with biogenic P, and their P‐normalized quotas were also strongly associated with lithogenic Al. The ratios of metals to Al and P for most of the bioactive trace metals were significantly higher than the ratios in lithogenic particles and than intracellular quotas in plankton, respectively, indicating that the trace metals in the sinking particles were abiogenic, nonlithogenic, and adsorbed on biogenic particles. The comparable fluxes between aeolian deposition and the sinking particles in the mixed layer demonstrate that the highly enriched trace metals in the sinking particles were attributed to input from anthropogenic aerosols. The coupling and transport of anthropogenic trace metals with biogenic particles in oceanic surface waters may be an important mechanism for trace metal cycling in global oceans.

Use of a GIS-based hybrid artificial neural network to prioritize the order of pipe replacement in a water distribution network - Cheng-I Ho; Min-Der Lin; Shang-Lien Lo (Environmental Monitoring and Assessment, 2010)

Cloning, expression and physiological analysis of broccoli catalase gene and Chinese cabbage ascorbate peroxidase gene under heat stress - Kuan-Hung Lin; Ho-Chang Huang; Ching-Yun Lin (Plant Cell Reports, 2010)

Two genetic divergence centers revealed by chloroplastic DNA variation in populations of Cinnamomum kanehirae Hay - Dai-Chang Kuo; Chia-Chia Lin; Kuo-Chieh Ho; Yu-Pin Cheng; Shih-Ying Hwang; Tsan-Piao Lin (Conservation Genetics, 2010)

Regeneration of soybean (Glycine max L. Merrill) through direct somatic embryogenesis from the immature embryonic shoot tip - Murugan Loganathan; Subbiyan Maruthasalam; Ling Yin Shiu; Wei Ching Lien; Wen Hwei Hsu; Pei Fang Lee; Chih Wen Yu; Chin Ho Lin (In Vitro Cellular & Developmental Biology - Plant, 2010)

Veterinary antibiotic sorption to agroforestry buffer, grass buffer and cropland soils - Bei Chu; Keith W. Goyne; Stephen H. Anderson; Chung-Ho Lin; Ranjith P. Udawatta (Agroforestry Systems, 2010)

Variation of biomass and kinetic parameters for nitrifying species in the TNCU3 process at different aerobic hydraulic retention times - Tzu-Yi Pai; Ren-Jie Chiou; Chwen-Jeng Tzeng; Tung-Sheng Lin; Shan-Chun Yeh; Pao-Jui Sung; Chu-Hui Tseng; Chia-Ho Tsai; Yao-Sheng Tsai; Wen-Jui Hsu; Yuh-Ling Wei (World Journal of Microbiology and Biotechnology, 2010)

Caligus ignotus n. sp. (Copepoda: Caligidae) parasitic on Poey’s scabbardfish Evoxymetopon poeyi (Günther) off Taiwan - Ju-shey Ho; Ching-Long Lin (Systematic Parasitology, 2010)

Lysine racemase: a novel non-antibiotic selectable marker for plant transformation - I-Chieh Chen; Venkatesan Thiruvengadam; Wei-De Lin; Ho-Hsiung Chang; Wen-Hwei Hsu (Plant Molecular Biology, 2010)

FORMOSAT-3/COSMIC observations of the ionospheric auroral oval development - Ho-Fang Tsai; Jann-Yenq Liu; Chien-Hung Lin; Mei-Lan Hsu (GPS Solutions, 2010)

Effects of compressive residual stress on the morphologic changes of fibroblasts - Shu-Li Lin; Jen-Chang Yang; Kuo-Ning Ho; Chau-Hsiang Wang; Chien-Wu Yeh; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2009)

Meat and egg consumption and risk of breast cancer among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Yu-Ming Chen; Fang-Yu Lin; Jian-Hua Fu; Shou-Zhen Cheng (Cancer Causes & Control, 2009)

Atmospheric Aerosols over a Southwestern Region of Texas - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; Rafael Tadmor; T. C. Ho (Environmental Modeling & Assessment, 2009)

Atmospheric Aerosol over a Southeastern Region of Texas: Chemical Composition and Possible Sources - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; T. C. Ho (Environmental Modeling & Assessment, 2009)

A negative regulator encoded by a rice WRKY gene represses both abscisic acid and gibberellins signaling in aleurone cells - Zhong-Lin Zhang; Margaret Shin; Xiaolu Zou; Jianzhi Huang; Tun-hua David Ho; Qingxi J. Shen (Plant Molecular Biology, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Impact of consistent boundary layer mixing approaches between NAM and CMAQ - Pius Lee; Youhua Tang; Daiwen Kang; Jeff McQueen; Marina Tsidulko; Ho-Chun Huang; Sarah Lu; Mary Hart; Hsin-Mu Lin; Shaocai Yu; Geoff DiMego; Ivanka Stajner; et al. (Environmental Fluid Mechanics, 2009)

Development of a Methodology for Strategic Environmental Assessment: Application to the Assessment of Golf Course Installation Policy in Taiwan - Ching-Ho Chen; Ray-Shyan Wu; Wei-Lin Liu; Wen-Ray Su; Yu-Min Chang (Environmental Management, 2009)

The Impact of Aqueous Solubility and Dose on the Pharmacokinetic Profiles of Resveratrol - Surajit Das; Hai-Shu Lin; Paul C. Ho; Ka-Yun Ng (Pharmaceutical Research, 2008)

The Impact of Aqueous Solubility and Dose on the Pharmacokinetic Profiles of Resveratrol - Surajit Das; Hai-Shu Lin; Paul C. Ho; Ka-Yun Ng (Pharmaceutical Research, 2008)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

A revision of the family Dissonidae Kurtz, 1924 (Copepoda: Siphonostomatoida) - Geoff A. Boxshall; Ching-Long Lin; Ju-Shey Ho; Susumu Ohtsuka; B. A. Venmathi Maran; Jean-Lou Justine (Systematic Parasitology, 2008)

Assessment of terrestrial factors controlling the submarine groundwater discharge in water shortage and highly deformed Island of Taiwan, Western Pacific Ocean - Tsung-Ren Peng; Chen-Tung Arthur Chen; Chung-Ho Wang; Jing Zhang; Yi-Jie Lin (Journal of Oceanography, 2008)

Residual Stress Patterns Affect Cell Distributions on Injection-Molded Poly-l-Lactide Substrate - Sheng-Yang Lee; How Tseng; Keng-Liang Ou; Jen-Chang Yang; Kuo-Ning Ho; Che-Tong Lin; Haw-Ming Huang (Annals of Biomedical Engineering, 2008)

Why are flood and landslide victims less willing to take mitigation measures than the public? - Shuyeu Lin; Daigee Shaw; Ming-Chou Ho (Natural Hazards, 2008)

Experiences of water transfer from the agricultural to the non-agricultural sector in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan; Y. L. Sung (Paddy and Water Environment, 2007)

Using EEFM (Excitation Emission Fluorescence Matrix) to Differentiate the Organic Properties of the Effluents from the Ozonated Biofilters - Wen-Liang Lai; Lih-Fu Chen; Shao-Wei Liao; Shu-Lin Hsu; Li-Ho Tseng; Chang-Ling Miaw (Water, Air, & Soil Pollution, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Three species of Caligus Müller, 1785 (Copepoda: Caligidae) parasitic on Caranx spp. (Teleostei: Carangidae) off Taiwan - Ju-shey Ho; Chin-Long Lin (Systematic Parasitology, 2007)

Ganoderma lucidum polysaccharide peptide reduced the production of proinflammatory cytokines in activated rheumatoid synovial fibroblast - Y. W. Ho; J. S. L. Yeung; P. K. Y. Chiu; W. M. Tang; Z. B. Lin; R. Y. K. Man; C. S. Lau (Molecular and Cellular Biochemistry, 2007)

Two new species of taeniacanthid copepods (Poecilostomatoida) parasitic on marine fishes of Taiwan - Ju-shey Ho; Ching-Long Lin (Systematic Parasitology, 2007)

Pleomorphic extra-renal manifestation of the glomerular podocyte marker podocalyxin in tissues of normal beagle dogs - Wei-Ling Lin; Victor Fei Pang; Chen-Hsuan Liu; Jen-Yau Chen; Kuo-Fang Shen; Yu-Yu Lin; Chun-Ying Yu; Yung-Ho Hsu; Tzuu-Shuh Jou (Histochemistry and Cell Biology, 2007)

Vertical ozone distributions observed using tethered ozonesondes in a coastal industrial city, Kaohsiung, in southern Taiwan - Ching-Ho Lin; Chin-Hsing Lai; Yee-Lin Wu; Hsin-Chih Lai; Po-Hsiung Lin (Environmental Monitoring and Assessment, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Alterations in health examination items and skin symptoms from exposure to ultra-low humidity - Tzu-Chieh Chou; Kuen-Huei Lin; Hamm-Min Sheu; Shih-Bin Su; Chia-Wei Lee; How-Ran Guo; Trong-Neng Wu; Ho-Yuan Chang (International Archives of Occupational and Environmental Health, 2007)

Sustainable Water Quality Management Framework and a Strategy Planning System for a River Basin - Ching-Ho Chen; Wei-Lin Liu; Horng-Guang Leu (Environmental Management, 2006)

Multifunctionality of paddy fields in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan (Paddy and Water Environment, 2006)

Aviglycine and propargylglycine inhibit conidial germination and mycelial growth of Fusarium oxysporumf. sp. luffae - Jung-Kang Jin; Douglas O. Adams; Yeong Ko; Chih-Wen Yu; Chin-Ho Lin (Mycopathologia, 2004)

A Method for Locating Influential Pollution Sources and Estimating Their Contributions - Ching-Ho Lin; Yee-Lin Wu; Ken-Hui Chang; Chin-Hsing Lai (Environmental Modeling & Assessment, 2004)

Production of an anti-complement exo-polymer produced by Auricularia auricula-judae in submerged culture - Sang-Chul Jeong; Sung-Pill Cho; Byung-Keun Yang; Young-Ah Gu; Jin-Ho Jang; Tae-Lin Huh; Chi-Hyun Song (Biotechnology Letters, 2004)

Fine-tuning risperidone dosage for acutely exacerbated schizophrenia: clinical determinants - Hsien-Yuan Lane; Yue-Cune Chang; Chih-Chiang Chiu; Sue-Hong Lee; Cher-Yeang Lin; Wen-Ho Chang (Psychopharmacology, 2004)

Actin filaments regulate the stretch sensitivity of large-conductance, Ca2+-activated K+ channels in coronary artery smooth muscle cells - Lin Piao; Won-Kyung Ho; Yung E. Earm (Pflügers Archiv - European Journal of Physiology, 2003)

Genistein protects primary cortical neurons from iron-induced lipid peroxidation - Kwok Ping Ho; Lin Li; Li Zhao; Zhong Ming Qian (Molecular and Cellular Biochemistry, 2003)

Comparison of soil nitrogen mineralization and nitrification in a mixed grassland and forested ecosystem in central Taiwan - Jeffrey S. Owen; Ming Kuang Wang; Hai Lin Sun; Hen Biau King; Chung Ho Wang; Chin Fang Chuang (Plant and Soil, 2003)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Naricolax insolitus n. sp., a bomolochid copepod (Poecilostomatoida) parasitic in the nasal cavities of silver pomfret Pampus argenteus off Taiwan - Ju-shey Ho; Ching-Long Lin (Systematic Parasitology, 2003)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Neurotoxicity of mercury sulfide in the vestibular ocular reflex system of guinea pigs - Jiunn-Jye Chuu; Yi-Ho Young; Shing-Hwa Liu; Shoei-Yn Lin-Shiau (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)

Enantioselective production of levofloxacin by immobilized porcine liver esterase - Sang-Yoon Lee; Byung-Hyuk Min; Sung-Ho Hwang; Yoon-Mo Koo; Choul-Kyun Lee; Seong-Won Song; Sun-Young Oh; Sang-Min Lim; Sang-Lin Kim; Dong-II Kim (Biotechnology Letters, 2001)

Heterotrimeric G-protein and signal transduction in the nematode-trapping fungus Arthrobotrys dactyloides - Tsung-Hsien Chen; Chan-San Hsu; Pui-Jen Tsai; Yi-Feng Ho; Na-Sheng Lin (Planta, 2001)

Species of Caligus Müller, 1785 (Copepoda: Caligidae) parasitic on marine fishes of Taiwan - Ju-shey Ho; Ching-Long Lin; Shiu-Nan Chen (Systematic Parasitology, 2000)

Azo dye decolorization with a mutant Escherichia coli strain - Jo-Shu Chang; Tai-Shin Kuo; Yun-Peng Chao; Jin-Yen Ho; Ping-Jei Lin (Biotechnology Letters, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)